Complex oxide and method for producing the same
By preparing composite oxides containing cerium, zirconium, aluminum and rare earth metal elements, the problem of degradation of OSC materials in high temperature environments is solved, efficient oxygen storage capacity is achieved, and the emission standards are improved.
Patent Information
- Application Number
- JP2024117903
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-28
- Filing Date
- 2024-07-23
- Publication Date
- 2025-02-07
AI Technical Summary
The performance of existing OSC materials in high temperature environments is degraded and it is difficult to meet increasingly stringent emission standards. Improved OSC materials are needed to improve their oxygen storage capacity in high temperature environments.
A composite oxide containing cerium, zirconium, aluminum and rare earth metal elements is prepared, and the particle size of aluminum compounds and the use of water-soluble polymers are controlled through a specific process to form a stable solid solution structure and improve oxygen storage capacity.
Under high temperature environment, the composite oxide exhibits excellent oxygen storage performance, with OSC amount reaching 1470 μmol/g or higher, significantly improving the emission treatment efficiency.
Smart Images

Figure 2025020026000001 
Figure 2025020026000002 
Figure 2025020026000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite oxide and a method for producing the same. [Background technology]
[0002] Exhaust gas emitted from internal combustion engines of automobiles, motorcycles, etc. contains harmful components such as hydrocarbons (HC), carbon monoxide (CO), nitrogen oxides (NOx), etc. Three-way catalysts, which have catalytic activity to oxidize HC and CO and convert them into water and carbon dioxide, and reduce NOx and convert it into nitrogen, are used as exhaust gas purification catalysts to purify and detoxify these harmful components.
[0003] In order to mitigate fluctuations in the oxygen concentration in exhaust gas and efficiently purify HC, CO, NOx, etc., materials with oxygen storage capacity (OSC: Oxygen Storage Capacity) (hereinafter sometimes referred to as "OSC materials") are used as constituent materials of three-way catalysts.
[0004] Composite oxides containing cerium, zirconium, aluminum, and possibly rare earth metal elements other than cerium are known as OSC materials (see, for example, Patent Document 1).
[0005] In Patent Document 1, the median diameter D measured by dynamic light scattering in the preparation of a composite oxide is 50 It is disclosed that the heat resistance of a composite oxide can be improved by using aluminum compound particles having a particle size of 1 nm or more and 220 nm or less. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2022 / 137910 Brochure Summary of the Invention [Problem to be solved by the invention]
[0007] Due to the increasing demand for exhaust gas purification performance in recent years, there is a demand for improving the performance of OSC materials.
[0008] The present invention aims to provide a composite oxide containing cerium, zirconium, aluminum, and optionally a rare earth metal element other than cerium, the composite oxide having improved OSC (particularly, OSC after exposure to a high-temperature environment), and a method for producing the composite oxide. [Means for solving the problem]
[0009] The present invention provides the following inventions. [1] A composite oxide containing cerium, zirconium, aluminum, and optionally a rare earth metal element other than cerium, CeO measured by CO pulse method 2 The composite oxide has an OSC amount per gram at 400° C. of 1470 μmol / g or more. [2] The following steps: (1a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, a cationic or nonionic water-soluble polymer, and optionally a rare earth metal salt other than a cerium salt; (1b) adding a precipitating agent to the raw material liquid to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium; (1c) separating the precipitate from the raw material liquid to obtain a cake containing the precipitate; and (1d) A step of calcining the cake to produce a composite oxide containing cerium, zirconium, aluminum, and optionally rare earth metal elements other than cerium. A method for producing a complex oxide, comprising: the aluminum compound particles are selected from alumina particles and alumina hydrate particles; The median diameter D of the aluminum compound particles measured by dynamic light scattering50 is 1 nm or more and 500 nm or less. [3] The manufacturing method according to [2], wherein in step (1a), the percentage of the amount of the water-soluble polymer in the raw material liquid relative to the amount of the aluminum compound particles in the raw material liquid is 0.1 mass% or more. [4] The following steps: (2a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt other than a cerium salt; (2b) adding a cationic or nonionic water-soluble polymer and a precipitant to the raw material liquid to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium; (2c) separating the precipitate from the raw material liquid to obtain a cake containing the precipitate; and (2d) A step of calcining the cake to produce a composite oxide containing cerium, zirconium, aluminum, and optionally rare earth metal elements other than cerium. A method for producing a complex oxide, comprising: In step (2b), the water-soluble polymer is added to the raw material liquid before the precipitate is formed; the aluminum compound particles are selected from alumina particles and alumina hydrate particles; The median diameter D of the aluminum compound particles measured by dynamic light scattering 50 is 1 nm or more and 500 nm or less. [5] The manufacturing method according to [4], wherein in step (2b), the percentage of the amount of the water-soluble polymer added to the raw material liquid relative to the amount of the aluminum compound particles in the raw material liquid is 0.1 mass% or more. [6] The method according to any one of [2] to [5], wherein the cationic water-soluble polymer has a repeating unit containing a quaternary ammonium group, and the molecular weight of the repeating unit is 180 or more. [7] The method according to [6], wherein the repeating unit has a weight average degree of polymerization of 20 or more. [8] The following steps: (3a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt other than the cerium salt; (3b) adding a precipitating agent to the raw material liquid to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium; (3c) separating the precipitate from the raw material liquid to obtain a cake containing the precipitate; (3d) mixing the cake with an anionic or nonionic water-soluble polymer in a solvent to obtain a slurry containing the water-soluble polymer; (3e) evaporating the slurry to dryness to obtain a dry product; and (3f) A step of calcining the dried product to produce a composite oxide containing cerium, zirconium, aluminum, and optionally rare earth metal elements other than cerium. A method for producing a complex oxide, comprising: the aluminum compound particles are selected from alumina particles and alumina hydrate particles; The median diameter D of the aluminum compound particles measured by dynamic light scattering 50 is 1 nm or more and 500 nm or less. [9] The manufacturing method described in [8], wherein in step (3d), the percentage of the amount of the water-soluble polymer mixed with the cake relative to the amount of solids in the cake is 5 mass% or more. Effect of the Invention
[0010] According to the present invention, there is provided a composite oxide containing cerium, zirconium, aluminum, and optionally a rare earth metal element other than cerium, the composite oxide having improved OSC (particularly, OSC after exposure to a high-temperature environment), and a method for producing the composite oxide. In this specification, "high temperature" means a temperature of preferably 800°C or higher, more preferably 900°C or higher, and even more preferably 1000°C or higher. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will now be described.
[0012] <Terminology explanation> The following describes terms used in this specification. The following descriptions apply to the entire specification unless otherwise specified.
[0013] <Rare earth metal elements> Rare earth metal elements means rare earth metal elements other than elemental cerium, unless otherwise specified.
[0014] <Rare earth metal ions> Rare earth metal ion means a rare earth metal ion other than cerium ion, unless otherwise specified.
[0015] <Rare earth metal salts> Rare earth metal salt means a rare earth metal salt other than a cerium salt, unless otherwise specified.
[0016] <Oxide> Cerium oxide is CeO 2 Zirconium oxide is ZrO 2 and aluminum oxide is Al 2 O 3 The oxides of rare earth metal elements are classified as sesquioxides (M 2 O 3 , M represents a rare earth metal element other than cerium, praseodymium, and terbium), and praseodymium oxide is Pr 6 O 11 Terbium oxide is Tb 4 O 7 means.
[0017] <Water-soluble salt> The solubility of the water-soluble salt in water at 20° C. (the mass of the water-soluble salt that can be dissolved in 100 g of water at 20° C.) is preferably 1.0 g or more, more preferably 2.0 g or more, and even more preferably 5.0 g or more.
[0018] <Poorly water-soluble salt> The solubility of the poorly water-soluble salt in water at 20° C. (the mass of the poorly water-soluble salt that can be dissolved in 100 g of water at 20° C.) is preferably less than 1.0 g, more preferably 0.5 g or less, and even more preferably 0.1 g or less.
[0019] <Water-soluble cerium salt> The water-soluble cerium salt can be selected from, for example, cerium chloride, cerium nitrate, cerium (III) sulfate, cerium acetate, and the like.
[0020] <Poorly water-soluble cerium salt> The poorly water-soluble cerium salt can be selected from, for example, cerium hydroxide, cerium oxide, cerium carbonate, cerium (IV) sulfate, etc. When the raw material liquid is acidic (for example, when an acid is generated by hydrolysis of a water-soluble rare earth metal salt and the raw material liquid becomes acidic), the poorly water-soluble cerium salt is preferably selected from cerium hydroxide and cerium carbonate, and more preferably cerium hydroxide, from the viewpoint of being soluble in the raw material liquid.
[0021] <Water-soluble zirconium salt> The water-soluble zirconium salt can be selected from, for example, zirconium oxychloride, zirconium chloride, zirconium oxynitrate, zirconium nitrate, zirconium oxyacetate, and the like.
[0022] <Slightly water-soluble zirconium salt> The poorly water-soluble zirconium salt can be selected from, for example, zirconium hydroxide, basic zirconium sulfate, zirconium oxide, basic zirconium carbonate, etc. When the raw material liquid is acidic (for example, when an acid is generated by hydrolysis of a water-soluble rare earth metal salt and the raw material liquid becomes acidic), the poorly water-soluble zirconium salt is preferably selected from zirconium hydroxide and basic zirconium carbonate in terms of being soluble in the raw material liquid, and more preferably zirconium hydroxide in terms of excellent mixability with aluminum compound particles.
[0023] <Water-soluble rare earth metal salts> The water-soluble rare earth metal salt means a water-soluble rare earth metal salt other than a water-soluble cerium salt, unless otherwise specified. The water-soluble rare earth metal salt can be selected from, for example, chlorides, nitrates, sulfates, acetates, etc. of rare earth metal elements. The sulfates of rare earth metal elements are preferably sulfates of trivalent rare earth metal elements.
[0024] <Poorly water-soluble rare earth metal salts> The poorly water-soluble rare earth metal salt means a poorly water-soluble rare earth metal salt other than a poorly water-soluble cerium salt, unless otherwise specified. The poorly water-soluble rare earth metal salt can be selected from, for example, hydroxides, oxides, carbonates, etc. of rare earth metal elements. When the raw material liquid is acidic (for example, when an acid is generated by hydrolysis of a water-soluble rare earth metal salt and the raw material liquid becomes acidic), from the viewpoint of being soluble in the raw material liquid, the poorly water-soluble rare earth metal salt is preferably selected from hydroxides and carbonates of rare earth metal elements, and more preferably is a hydroxide of a rare earth metal element.
[0025] <Aluminum compound particles> The aluminum compound particles may be selected from alumina particles and alumina hydrate particles.
[0026] The alumina hydrate constituting the alumina hydrate particles can be selected from, for example, alumina monohydrate, alumina trihydrate, and the like.
[0027] Alumina monohydrate is typically AlO(OH), α-Al 2 O 3 H 2 Alumina monohydrate is represented by a composition formula such as O. The alumina monohydrate can be selected from, for example, boehmite, diaspore, etc. The boehmite may be so-called pseudoboehmite containing one or more water molecules between layers.
[0028] Alumina trihydrate is typically Al(OH) 3 , Al 2 O 3 3H 2O. The alumina trihydrate can be selected from, for example, gibbsite (also called hydrargillite), bayerite, and the like.
[0029] <Median diameter of aluminum compound particles D 50 > Median diameter D of aluminum compound particles measured by dynamic light scattering method 50 means the particle size at which the cumulative volume is 50% in the volume-based particle size distribution of aluminum compound particles measured by dynamic light scattering. Measurement of the volume-based particle size distribution of aluminum compound particles by dynamic light scattering is performed by dispersing aluminum compound particles in 1.5 mass% hydrochloric acid (1.5 mass% HCl aqueous solution) and using a commercially available particle size distribution measuring device (e.g., "Zetasizer Nano ZS" manufactured by Malvern Panalytical). That is, the median diameter D of aluminum compound particles measured by dynamic light scattering is 50 is the median diameter D of the aluminum compound particles measured by dynamic light scattering after dispersing the aluminum compound particles in 1.5 mass % hydrochloric acid. 50 means...
[0030] <Water-soluble polymer> The water-soluble polymer means a water-soluble organic compound having a weight-average molecular weight of 5,000 or more.
[0031] The solubility of the water-soluble polymer in water at 20° C. (the mass of the water-soluble polymer that can be dissolved in 100 g of water at 20° C.) is preferably 1.0 g or more, more preferably 2.0 g or more, and even more preferably 5.0 g or more.
[0032] The water-soluble polymer may be a homopolymer or a copolymer, for example, a random copolymer, an alternating copolymer, a block copolymer, a graft copolymer, and the like.
[0033] <Weight average molecular weight> The weight average molecular weight of the water-soluble polymer can be measured by gel permeation chromatography (GPC) using polystyrene as a standard substance.
[0034] <Weight average degree of polymerization> In the case of a homopolymer, the weight average degree of polymerization of the repeating unit can be determined by dividing the weight average molecular weight of the homopolymer by the molecular weight of the repeating unit. In the case of a copolymer, the weight average degree of polymerization of each repeating unit can be determined by 1 It can be determined based on the results of H-NMR analysis.
[0035] <Alkyl group> The alkyl group may be linear or branched. The alkyl group may have one or more substituents. The number of carbon atoms in the alkyl group is, for example, 1 to 10, preferably 1 to 6, more preferably 1 to 4, even more preferably 1 to 3, even more preferably 1 to 2, and even more preferably 1. When the alkyl group has a substituent, the number of carbon atoms in the alkyl group does not include the number of carbon atoms in the substituent.
[0036] <Cycloalkyl group> The cycloalkyl group may be monocyclic or polycyclic (e.g., bicyclic), but is preferably monocyclic. The cycloalkyl group may have one or more substituents. The number of carbon atoms in the cycloalkyl group is, for example, 3 to 10, preferably 3 to 6, more preferably 3 to 4, and even more preferably 4. When the cycloalkyl group has a substituent, the number of carbon atoms in the cycloalkyl group does not include the number of carbon atoms in the substituent.
[0037] <Alkenyl group> The alkenyl group may be linear or branched. The alkenyl group may have one or more substituents. The number of carbon atoms in the alkenyl group is, for example, 2 to 10, preferably 2 to 6, more preferably 2 to 4, even more preferably 2 to 3, and even more preferably 2. When the alkenyl group has a substituent, the number of carbon atoms in the alkenyl group does not include the number of carbon atoms in the substituent.
[0038] <Cycloalkenyl group> The cycloalkenyl group may be monocyclic or polycyclic (e.g., bicyclic), but is preferably monocyclic. The cycloalkenyl group may have one or more substituents. The number of carbon atoms in the cycloalkenyl group is, for example, 3 to 10, preferably 3 to 6, more preferably 3 to 4, and even more preferably 4. When the cycloalkenyl group has a substituent, the number of carbon atoms in the cycloalkenyl group does not include the number of carbon atoms in the substituent.
[0039] <Alkynyl group> The alkynyl group may be linear or branched. The alkynyl group may have one or more substituents. The number of carbon atoms in the alkynyl group is, for example, 2 to 10, preferably 2 to 6, more preferably 2 to 4, even more preferably 2 to 3, and even more preferably 2. When the alkynyl group has a substituent, the number of carbon atoms in the alkynyl group does not include the number of carbon atoms in the substituent.
[0040] <Cycloalkynyl group> The cycloalkynyl group may be monocyclic or polycyclic (e.g., bicyclic), but is preferably monocyclic. The cycloalkynyl group may have one or more substituents. The number of carbon atoms in the cycloalkynyl group is, for example, 3 to 10, preferably 3 to 6, more preferably 3 to 4, and even more preferably 4. When the cycloalkynyl group has a substituent, the number of carbon atoms in the cycloalkynyl group does not include the number of carbon atoms in the substituent.
[0041] <Aryl group> The aryl group is, for example, a monocyclic or polycyclic (e.g., bicyclic or tricyclic) aromatic hydrocarbon ring group having 4 to 20 carbon atoms. The polycyclic group may be a condensed ring. The aryl group may have one or more substituents. Examples of the aryl group include a phenyl group and a naphthyl group. The number of carbon atoms in the aryl group is, for example, 6 to 20, preferably 6 to 14, more preferably 6 to 12, and even more preferably 6 to 10. When the aryl group has a substituent, the number of carbon atoms in the aryl group does not include the number of carbon atoms of the substituent.
[0042] <Aryl alkyl group> The arylalkyl group is an alkyl group having one or more aryl groups, and the explanation of the alkyl group and the aryl group is as above. The number of aryl groups in the arylalkyl group is, for example, 1, 2 or 3. The arylalkyl group may have one or more substituents.
[0043] <Arylalkenyl group> The arylalkenyl group is an alkenyl group having one or more aryl groups, and the explanation of the alkenyl group and the aryl group is as above. The number of aryl groups in the arylalkenyl group is, for example, 1, 2 or 3. The arylalkenyl group may have one or more substituents.
[0044] <Arylalkynyl group> The arylalkynyl group is an alkynyl group having one or more aryl groups, and the explanation of the alkynyl group and the aryl group is as described above. The number of aryl groups in the arylalkynyl group is, for example, 1, 2 or 3. The arylalkynyl group may have one or more substituents.
[0045] <Alkylaryl group> The alkylaryl group is an aryl group having one or more alkyl groups, and the explanation of the alkyl group and the aryl group is as above. The number of alkyl groups in the alkylaryl group is, for example, 1, 2 or 3. The alkylaryl group may have one or more substituents.
[0046] <Alkenylaryl group> The alkenylaryl group is an aryl group having one or more alkenyl groups, and the explanation of the alkenyl group and the aryl group is as above. The number of alkenyl groups in the alkenylaryl group is, for example, 1, 2 or 3. The alkenylaryl group may have one or more substituents.
[0047] <Alkynylaryl group> The alkynylaryl group is an aryl group having one or more alkynyl groups, and the explanation of the alkynyl group and the aryl group is as above. The number of alkynyl groups in the alkynylaryl group is, for example, 1, 2 or 3. The alkynylaryl group may have one or more substituents.
[0048] <One or more substituents> The number of one or more substituents may be, for example, one, two or three.
[0049] The one or more substituents can be selected from, for example, halogen atoms, alkyl groups, haloalkyl groups, alkyloxy groups, haloalkyloxy groups, alkylthio groups, haloalkylthio groups, nitro groups, nitroalkyl groups, phenyl groups, halophenyl groups, phenol groups, and the like.
[0050] The halogen atom can be selected from a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. The alkyl group is as described above. The haloalkyl group is an alkyl group having one or more halogen atoms, and the alkyl group and the halogen atom are as described above. The number of halogen atoms in the haloalkyl group is, for example, 1, 2, or 3. The alkyloxy group is a group represented by the formula: -O-alkyl group, and the alkyl group is as described above. The haloalkyloxy group is a group represented by the formula: -O-haloalkyl group, and the haloalkyl group is as described above. The alkylthio group is a group represented by the formula: -S-alkyl group, and the alkyl group is as described above. The haloalkylthio group is a group represented by the formula: -S-haloalkyl group, and the haloalkyl group is as described above. The halophenyl group is a phenyl group having one or more halogen atoms, and the halogen atom is as described above. The number of halogen atoms in the halophenyl group is, for example, 1, 2, or 3.
[0051] The one or more substituents are each independently preferably selected from a halogen atom, an alkyl group having 1 to 3 carbon atoms, a haloalkyl group having 1 to 3 carbon atoms, an alkyloxy group having 1 to 3 carbon atoms, a haloalkyloxy group having 1 to 3 carbon atoms, an alkylthio group having 1 to 3 carbon atoms, and a haloalkylthio group having 1 to 3 carbon atoms, more preferably selected from a halogen atom, an alkyl group having 1 to 3 carbon atoms, a haloalkyl group having 1 to 3 carbon atoms, an alkyloxy group having 1 to 3 carbon atoms, and a haloalkyloxy group having 1 to 3 carbon atoms, and even more preferably selected from a halogen atom, an alkyl group having 1 to 3 carbon atoms, and an alkyloxy group having 1 to 3 carbon atoms.
[0052] <Complex oxide> The composite oxide of the present invention will now be described.
[0053] The composite oxide of the present invention contains elemental cerium, elemental zirconium, elemental aluminum, and optionally, a rare earth metal element.
[0054] The composite oxide of the present invention may be in the form of, for example, powder.
[0055] From the viewpoint of improving the OSC of the composite oxide of the present invention, the content of cerium element in the composite oxide of the present invention, calculated as cerium oxide, based on the mass of the composite oxide of the present invention, is preferably 1.0 mass% or more and 50 mass% or less, more preferably 3.0 mass% or more and 40 mass% or less, and even more preferably 5.0 mass% or more and 30 mass% or less.
[0056] From the viewpoint of improving the heat resistance of the composite oxide of the present invention, the content of zirconium element in the composite oxide of the present invention, calculated as zirconium oxide, based on the mass of the composite oxide of the present invention, is preferably 1.0 mass% or more and 70 mass% or less, more preferably 10 mass% or more and 60 mass% or less, and even more preferably 20 mass% or more and 45 mass% or less.
[0057] From the viewpoint of achieving a balance between the OSC and heat resistance in the composite oxide of the present invention, the ratio of the content of zirconium element, calculated as zirconium oxide, to the content of cerium element, calculated as cerium oxide, is preferably 0.10 or more and 20 or less, more preferably 0.70 or more and 10 or less, and even more preferably 1.3 or more and 5.0 or less.
[0058] From the viewpoint of improving the heat resistance of the composite oxide of the present invention, the content of aluminum element in the composite oxide of the present invention, calculated as aluminum oxide, based on the mass of the composite oxide of the present invention, is preferably 20 mass% or more and 90 mass% or less, more preferably 30 mass% or more and 80 mass% or less, even more preferably 40 mass% or more and 70 mass% or less, and even more preferably 40 mass% or more and 60 mass% or less.
[0059] From the viewpoint of achieving a balance between the OSC and heat resistance in the composite oxide of the present invention, the ratio of the content of aluminum element, calculated as aluminum oxide, to the sum of the content of cerium element, calculated as cerium oxide, and the content of zirconium element, calculated as zirconium oxide, is preferably 0.10 or more and 9.0 or less, more preferably 0.50 or more and 4.0 or less, even more preferably 0.60 or more and 2.3 or less, and even more preferably 0.60 or more and 1.9 or less.
[0060] The composite oxide of the present invention may contain one, two, or three or more rare earth metal elements.
[0061] The rare earth metal element can be selected from, for example, yttrium, praseodymium, scandium, lanthanum, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, and the like.
[0062] In one embodiment, the composite oxide of the present invention can contain one, two, or three or more rare earth metal elements selected from the group consisting of lanthanum, neodymium, praseodymium, and yttrium.
[0063] From the viewpoint of improving the OSC and heat resistance of the composite oxide of the present invention, the content of the rare earth metal element in the composite oxide of the present invention, calculated as an oxide, is preferably 0.1% by mass to 30.0% by mass, more preferably 1.0% by mass to 25.0% by mass, and even more preferably 5.0% by mass to 20.0% by mass, based on the mass of the composite oxide of the present invention. The content of the rare earth metal element in the composite oxide of the present invention, calculated as an oxide, means the content of the one rare earth metal element in the composite oxide of the present invention when the composite oxide of the present invention contains one rare earth metal element, and means the total content of the two or more rare earth metal elements in the oxide form when the composite oxide of the present invention contains two or more rare earth metal elements.
[0064] In the composite oxide of the present invention, the cerium element may form a solid solution phase (e.g., a solid solution phase of cerium oxide and zirconium oxide) or a single phase which is a crystalline phase or an amorphous phase (e.g., a single phase of cerium oxide), but it is preferable that at least a part of the cerium element forms a solid solution phase.
[0065] In the composite oxide of the present invention, the zirconium element may form a solid solution phase (e.g., a solid solution phase of cerium oxide and zirconium oxide) or a single phase which is a crystalline phase or an amorphous phase (e.g., a single phase of zirconium oxide), but it is preferable that at least a part of the zirconium element forms a solid solution phase.
[0066] In the composite oxide of the present invention, the aluminum element may form a solid solution phase together with the cerium element and / or zirconium element (e.g., a solid solution phase of cerium oxide, zirconium oxide, and aluminum oxide, a solid solution phase of cerium oxide and aluminum oxide, a solid solution phase of zirconium oxide and aluminum oxide, etc.), or may form a single phase which is a crystalline phase or an amorphous phase (e.g., an aluminum oxide single phase).
[0067] In the composite oxide of the present invention, the rare earth metal element may form a solid solution phase together with cerium element and / or zirconium element (e.g., a solid solution phase of cerium oxide, zirconium oxide, and an oxide of a rare earth metal element, a solid solution phase of cerium oxide and an oxide of a rare earth metal element, a solid solution phase of zirconium oxide and an oxide of a rare earth metal element, etc.), or may form a single phase which is a crystalline phase or an amorphous phase (e.g., an oxide of a rare earth metal element).
[0068] When the composite oxide of the present invention exists alone, the content of each element in the composite oxide of the present invention in terms of oxide can be determined by dissolving the composite oxide of the present invention by alkali fusion or the like, measuring the content of each element in a molten product by a conventional method such as inductively coupled plasma atomic emission spectrometry (ICP-AES), and determining the content of each element measured.
[0069] When the composite oxide of the present invention exists together with other components (for example, when the composite oxide of the present invention exists in a catalyst layer), the content of each element in the composite oxide of the present invention calculated as an oxide can be determined by analyzing a sample containing the composite oxide of the present invention (for example, a sample obtained from a catalyst layer) by energy dispersive X-ray spectroscopy (EDX) and obtaining elemental mapping and EDX elemental analysis of a specified particle. Specifically, the composite oxide particles of the present invention and other particles are qualitatively identified (color-coded) by elemental mapping, and the specified particles are subjected to composition analysis (elemental analysis), thereby determining the content of each element in the specified particles calculated as an oxide.
[0070] CeO measured by CO pulse method 2 The amount of OSC of the composite oxide of the present invention per gram at 400° C. is preferably 1470 μmol / g or more, more preferably 1480 μmol / g or more, even more preferably 1490 μmol / g or more, and even more preferably 1500 μmol / g or more. The upper limit is not particularly limited, and is, for example, 2500 μmol / g or less.
[0071] CeO measured by CO pulse method 2 A composite oxide having an OSC amount of 1470 μmol / g or more per gram at 400° C. can exhibit excellent OSC (particularly, OSC after exposure to a high-temperature environment).
[0072] The amount of OSC in a composite oxide can be measured by the CO pulse method as follows.
[0073] A sample is prepared by carrying 1 part by mass of rhodium element, calculated as metal, on the composite oxide, per 100 parts by mass of the composite oxide, and then heat-treating the composite oxide in air at 1000°C for 25 hours. Specifically, the composite oxide of the present invention is dispersed in an aqueous solution of a water-soluble rhodium salt (e.g., rhodium nitrate), and the solvent is evaporated while stirring. The mixture is then fired in air at 600°C for 1 hour to prepare a powder carrying 1 part by mass of rhodium element, calculated as metal, per 100 parts by mass of the composite oxide. The prepared powder is then heat-treated in air at 1000°C for 25 hours to prepare a sample.
[0074] The sample is packed into a sample tube and heated to 800°C under an argon gas flow, and then cooled to 400°C. The sample thus obtained at 400°C is used to carry out the following operation (A) to obtain CeO 2 The amount of OSC per 1g was calculated and 2 The amount of OSC in the composite oxide at 400°C per 1g.
[0075] [Operation(A)] Oxygen was passed through the sample tube, followed by helium, and then a mixed gas (1 atm, 0°C) containing 25% by volume of CO and 75% by volume of helium was passed through the sample tube at a flow rate of 50 cc / min 15 times to measure the CeO 2 and Rh 2 O 3 The amount of CO contained in the gas after contact is measured, and the amount of CO reduction (μmol) is calculated. The measurement device used is a Microtrack Bell "BELMETAL". Using the amount of CO reduction calculated by the above procedure, the CeO 2 Calculate the amount of OSC per gram (μmol / g). CEO 2 Amount of OSC per 1g = amount of CO reduced (μmol) / CeO in sample 2 Content (g)
[0076] CEO 2The OSC of a composite oxide can be evaluated by using the amount of OSC of the composite oxide at 400°C per 1g as an index. That is, when a CO / helium mixed gas is contacted with a composite oxide carrying rhodium element, (1) 2CeO 2 +CO→Ce 2 O 3 +CO 2 , and (2) Rh 2 O 3 +3CO → 2Rh+3CO 2 The reaction (2) proceeds independently of the OSC of the complex oxide. Therefore, the amount of reaction (1) caused by the complex oxide (i.e., the OSC of the complex oxide) can be evaluated by measuring the amount of CO reduction.
[0077] The composite oxide of the present invention can be used as a component of a catalyst for purifying exhaust gas.
[0078] In one embodiment, the exhaust gas purification catalyst contains one or more precious metal elements and the composite oxide of the present invention. The amounts of the precious metal elements and the composite oxide of the present invention contained in the exhaust gas purification catalyst can be appropriately adjusted.
[0079] The precious metal element can be selected from, for example, palladium, platinum, rhodium, ruthenium, osmium, iridium, etc. The precious metal element is supported on the composite oxide of the present invention in a form capable of functioning as a catalytically active component, for example, in the form of a catalytically active component containing a precious metal element, such as a precious metal, an alloy containing a precious metal element, or a compound containing a precious metal element (for example, an oxide of a precious metal element). The catalytically active component containing a precious metal element is preferably in the form of particles from the viewpoint of enhancing exhaust gas purification performance.
[0080] At least a part of the catalytically active component is preferably supported on the composite oxide of the present invention.
[0081] "At least a part of the catalytically active component is supported on the composite oxide of the present invention" means that at least a part of the catalytically active component is physically and / or chemically adsorbed or held on the outer surface and / or inner surface of the pores of the composite oxide of the present invention. The fact that at least a part of the catalytically active component is supported on the support can be confirmed, for example, by using a scanning electron microscope-energy dispersive X-ray analysis method (SEM-EDX). Specifically, when at least a part of the catalytically active component and the support are present in the same region in element mapping obtained by analyzing a cross section of the exhaust gas purification catalyst with SEM-EDX, it can be determined that at least a part of the catalytically active component is supported on the support.
[0082] The exhaust gas purifying catalyst may contain a carrier component other than the complex oxide of the present invention. When the exhaust gas purifying catalyst contains a carrier component other than the complex oxide of the present invention, at least a part of the catalytically active component may be supported on the carrier component other than the complex oxide of the present invention. The carrier component other than the complex oxide of the present invention may be, for example, alumina (Al 2 O 3 ), modified alumina, oxides of rare earth metal elements, zirconia (ZrO 2 ), silica (SiO 2 ), titania (TiO 2 ), zeolite (aluminosilicate), MgO, ZnO, SnO 2 The modified alumina can be selected from oxides based on alumina-silica, alumina-silicate, alumina-zirconia, alumina-chromia, alumina-ceria, alumina-lanthana, and the like.
[0083] The exhaust gas purifying catalyst may contain other components such as a stabilizer and a binder.
[0084] In one embodiment, the exhaust gas purification catalyst is a molded body having a shape such as a pellet. The exhaust gas purification catalyst according to this embodiment can be produced, for example, by drying and calcining the exhaust gas purification catalyst composition. The drying temperature, drying time, calcination temperature and calcination time can be appropriately adjusted. Calcination can be carried out, for example, under air atmosphere.
[0085] In another embodiment, the exhaust gas purification catalyst comprises a substrate and a catalyst layer formed on the substrate, and the catalyst layer contains one or more kinds of precious metal elements and the composite oxide of the present invention.
[0086] The substrate can be appropriately selected from substrates used in known exhaust gas purification catalysts. The substrate material can be, for example, alumina (Al 2 O 3 ), Mullite (3Al 2 O 3 -2SiO 2 ), cordierite (2MgO-2Al 2 O 3 -5SiO 2 ), Aluminum titanate (Al 2 TiO 5 ), ceramics such as silicon carbide (SiC), metal materials such as stainless steel, etc. The shape of the substrate can be selected from, for example, a honeycomb shape, a pellet shape, a sphere shape, etc. When using a honeycomb substrate, for example, a monolith substrate having a large number of parallel fine gas flow passages, i.e., channels, inside the substrate can be used so that a fluid flows inside the substrate.
[0087] The catalyst layer can be formed by applying the exhaust gas purification catalyst composition to the surface of the substrate, drying and firing. For example, when a monolithic substrate is used, the exhaust gas purification catalyst composition is applied to the inner wall surface of each channel of the monolithic substrate, followed by drying and firing to form a catalyst layer on the inner wall surface of each channel of the monolithic substrate. The catalyst layer can also be produced by a method in which the layer obtained by applying the exhaust gas purification catalyst composition to the substrate surface, drying and firing is impregnated with a solution containing a precious metal salt, followed by drying and firing. The drying temperature, drying time, firing temperature and firing time can be appropriately adjusted. The firing can be carried out, for example, under an air atmosphere.
[0088] The exhaust gas purification catalyst composition used in the production of the exhaust gas purification catalyst is, for example, a slurry containing a salt of a precious metal element and the composite oxide of the present invention. The salt of the precious metal element can be selected from, for example, a nitrate, an ammine complex salt, a chloride, etc. The solvent contained in the dispersion can be selected from, for example, water, an organic solvent, etc.
[0089] <Method for producing composite oxide> The method for producing the composite oxide of the present invention will now be described.
[0090] The method for producing a complex oxide of the present invention includes a first, second and third production methods.
[0091] <First manufacturing method> The first manufacturing method will now be described.
[0092] The first method includes the following steps: (1a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, a cationic or nonionic water-soluble polymer, and optionally a rare earth metal salt; (1b) adding a precipitating agent to the raw material solution prepared in step (1a) to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal; (1c) separating the precipitate from the raw material liquid subjected to step (1b) to obtain a cake containing the precipitate; and (1d) A step of calcining the cake obtained in step (1c) to produce a composite oxide containing cerium, zirconium, aluminum, and optionally rare earth metal elements. Includes.
[0093] In the raw material solution prepared in step (1a), the cationic or nonionic water-soluble polymer is adsorbed to the surface of the positively charged aluminum compound particles with moderate strength, not with excessive strength. The water-soluble polymer adsorbed to the surface of the aluminum compound particles preferably forms a water-soluble polymer layer.
[0094] The precipitate formed in step (1b) and the cake obtained in step (1c) contain poorly water-soluble salt particles and aluminum compound particles in a mixed state. Examples of poorly water-soluble salt particles include composite salt particles containing poorly water-soluble cerium salt, poorly water-soluble zirconium salt, and optionally poorly water-soluble rare earth metal salt, poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles, etc. From the viewpoint of improving the OSC of the composite oxide produced in step (1d), it is preferable that the precipitate and the cake contain composite salt particles. The precipitate and the cake may contain poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles, etc. in addition to the composite salt particles.
[0095] The water-soluble polymer adsorbed on the surface of the aluminum compound particles (preferably a water-soluble polymer layer formed on the surface of the aluminum compound particles) effectively suppresses aggregation of the aluminum compound particles, thereby improving the dispersibility of the aluminum compound particles in the precipitate formed in step (1b) and the cake obtained in step (1c).
[0096] In the precipitate formed in step (1b) and the cake obtained in step (1c), the poorly water-soluble salt particles are surrounded by aluminum compound particles and water-soluble polymers (preferably water-soluble polymer layers formed on the surfaces of the aluminum compound particles) adsorbed on the surfaces of the aluminum compound particles, which effectively suppresses contact between the poorly water-soluble salt particles. The above-mentioned improvement in dispersibility of the aluminum compound particles also contributes to the suppression of contact between the poorly water-soluble salt particles. By effectively suppressing contact between the poorly water-soluble salt particles, sintering between the poorly water-soluble salt particles is effectively suppressed when the cake is baked in step (1d), and the decrease in the specific surface area of the complex oxide caused by the sintering between the poorly water-soluble salt particles and the decrease in the OSC of the complex oxide caused by the decrease in the specific surface area of the complex oxide are effectively suppressed. Therefore, according to the first manufacturing method, a complex oxide with improved OSC can be manufactured. The first manufacturing method is suitable as a manufacturing method for the complex oxide of the present invention.
[0097] If the raw material liquid prepared in step (1a) does not contain a cationic or nonionic water-soluble polymer, or if it contains a low molecular weight compound instead of a cationic or nonionic water-soluble polymer, contact between the poorly water-soluble salt particles cannot be effectively suppressed in the precipitate formed in step (1b) and in the cake obtained in step (1c), and sintering between the poorly water-soluble salt particles cannot be effectively suppressed when the cake is baked in step (1d).
[0098] When the raw material liquid prepared in step (1a) contains an anionic water-soluble polymer instead of a cationic or nonionic water-soluble polymer, the anionic water-soluble polymer binds excessively strongly to the positively charged aluminum compound particles, causing the aluminum compound particles to aggregate with each other. As a result, contact between the poorly water-soluble salt particles cannot be effectively suppressed in the precipitate formed in step (1b) and in the cake obtained in step (1c), and sintering between the poorly water-soluble salt particles cannot be effectively suppressed when the cake is baked in step (1d).
[0099] If the raw material liquid prepared in step (1a) does not contain a cationic or nonionic water-soluble polymer, and a cationic or nonionic water-soluble polymer is added to the raw material liquid when a precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element is formed in step (1b) or after the precipitate is formed, contact between the poorly water-soluble salt particles cannot be effectively suppressed in the precipitate formed in step (1b) and the cake obtained in step (1c), and sintering between the poorly water-soluble salt particles cannot be effectively suppressed when the cake is baked in step (1d).
[0100] Steps (1a) to (1d) will be described below.
[0101] Engineering (1a) Step (1a) is a step of preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, a cationic or nonionic water-soluble polymer, and optionally a rare earth metal salt.
[0102] In the raw material solution prepared in step (1a), the cationic or nonionic water-soluble polymer is adsorbed to the surface of the positively charged aluminum compound particles with moderate strength, not with excessive strength. The water-soluble polymer adsorbed to the surface of the aluminum compound particles preferably forms a water-soluble polymer layer.
[0103] Step (1a) may include a step of preparing a raw material liquid. For example, the raw material liquid can be prepared by mixing a cerium salt, a zirconium salt, aluminum compound particles, a cationic or nonionic water-soluble polymer, and optionally a rare earth metal salt in water. The order of mixing the components is not particularly limited. For example, the raw material liquid can be prepared by mixing aluminum compound particles and a cationic or nonionic water-soluble polymer in water, and then adding and mixing a cerium salt, a zirconium salt, and optionally a rare earth metal salt to the resulting mixture. Alternatively, the raw material liquid can be prepared by dispersing aluminum compound particles in water, adding and mixing a cationic or nonionic water-soluble polymer to the resulting dispersion, and adding and mixing a cerium salt, a zirconium salt, and optionally a rare earth metal salt to the resulting mixture.
[0104] From the viewpoint of obtaining a desired precipitate in step (1b), the raw material liquid is preferably stirred to disperse the aluminum compound particles in the raw material liquid before being subjected to step (1b).
[0105] The water contained in the raw material liquid is preferably pure water such as ion-exchanged water. The raw material liquid may contain one or more solvents other than water. The solvent other than water can be selected from organic solvents such as alcohol, acetone, dimethyl sulfoxide, and dimethylformamide. The total amount of one or more solvents other than water is not particularly limited as long as the water-soluble salt can be dissolved in the raw material liquid, but is usually 50.0 vol% or less, preferably 20.0 vol% or less, based on the volume of the raw material liquid.
[0106] The cerium salt and the zirconium salt contained in the raw material liquid may be either a water-soluble salt or a poorly water-soluble salt, but it is preferable that at least one of the cerium salt and the zirconium salt is a water-soluble salt, and it is more preferable that both of the cerium salt and the zirconium salt are water-soluble salts. The rare earth metal salt optionally contained in the raw material liquid may be either a water-soluble salt or a poorly water-soluble salt, but it is preferable that it is a water-soluble salt.
[0107] The raw material liquid may contain one kind of water-soluble cerium salt or may contain two or more kinds of water-soluble cerium salts. The amount of the water-soluble cerium salt contained in the raw material liquid is appropriately adjusted so that the content of cerium element in the composite oxide produced in step (1d) is within a desired range, calculated as cerium oxide.
[0108] The raw material liquid may contain one type of poorly water-soluble cerium salt or two or more types of poorly water-soluble cerium salts. The amount of the poorly water-soluble cerium salt contained in the raw material liquid is appropriately adjusted so that the content of cerium element in the composite oxide produced in step (1d) in terms of cerium oxide falls within a desired range.
[0109] The raw material liquid may contain one kind of water-soluble zirconium salt or may contain two or more kinds of water-soluble zirconium salts. The amount of the water-soluble zirconium salt contained in the raw material liquid is appropriately adjusted so that the content of zirconium element in the composite oxide produced in step (1d) is within a desired range, calculated as zirconium oxide.
[0110] The raw material liquid may contain one type of poorly water-soluble zirconium salt or two or more types of poorly water-soluble zirconium salts. The amount of the poorly water-soluble zirconium salt contained in the raw material liquid is appropriately adjusted so that the content of zirconium element in the composite oxide produced in step (1d) in terms of zirconium oxide falls within a desired range.
[0111] The raw material liquid may contain one kind of water-soluble rare earth metal salt, or may contain two or more kinds of water-soluble rare earth metal salts. The amount of the water-soluble rare earth metal salt contained in the raw material liquid is appropriately adjusted so that the content of the rare earth metal element in the composite oxide produced in step (1d) in terms of oxide falls within a desired range.
[0112] The raw material liquid may contain one type of poorly water-soluble rare earth metal salt, or may contain two or more types of poorly water-soluble rare earth metal salts. The amount of the poorly water-soluble rare earth metal salt contained in the raw material liquid is appropriately adjusted so that the content of the rare earth metal element in the composite oxide produced in step (1d) in terms of oxide falls within a desired range.
[0113] The aluminum compound particles contained in the raw material liquid may be composed of either alumina particles or alumina hydrate particles, or may be composed of both, but from the viewpoint of improving the OSC of the composite oxide produced in step (1d), it is preferable that they are composed of alumina hydrate particles. Alumina hydrate particles have low sinterability and are easily finely dispersed in the composite oxide, which is advantageous in improving the OSC of the composite oxide.
[0114] From the viewpoint of improving the OSC of the composite oxide produced in step (1d), the alumina hydrate constituting the alumina hydrate particles is preferably alumina monohydrate or alumina trihydrate, and more preferably alumina monohydrate.
[0115] From the viewpoint of improving the OSC of the composite oxide produced in the step (1d), the alumina monohydrate is preferably boehmite.
[0116] Median diameter D of aluminum compound particles contained in the raw material liquid 50 is preferably 1 nm or more and 500 nm or less, more preferably 5 nm or more and 400 nm or less, even more preferably 10 nm or more and 350 nm or less, and even more preferably 15 nm or more and 300 nm or less. 50 When the median diameter D of the aluminum compound particles is within the above range, the dispersibility of the aluminum compound particles in the precipitate formed in step (1b) and the cake obtained in step (1c) can be improved, and thus the OSC of the composite oxide produced in step (1d) can be improved. 50 is measured by dynamic light scattering.
[0117] The raw material liquid contains a cationic or nonionic water-soluble polymer. "The raw material liquid contains a cationic or nonionic water-soluble polymer" includes embodiments in which the raw material liquid contains one or more cationic water-soluble polymers and no nonionic water-soluble polymers, embodiments in which the raw material liquid contains one or more nonionic water-soluble polymers and no cationic water-soluble polymers, and embodiments in which the raw material liquid contains one or more cationic water-soluble polymers and one or more nonionic water-soluble polymers.
[0118] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the percentage of the amount of water-soluble polymer in the raw liquid relative to the amount of aluminum compound particles in the raw liquid is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more. The upper limit can be appropriately adjusted, but is preferably 200% by mass or less, more preferably 100% by mass or less, and even more preferably 50% by mass or less. Each of these upper limits may be combined with any of the above-mentioned lower limits. When the raw liquid contains one type of aluminum compound particles, the "amount of aluminum compound particles in the raw liquid" means the amount of the one type of aluminum compound particles, and when the raw liquid contains two or more types of aluminum compound particles, it means the total amount of the two or more types of aluminum compound particles. The "amount of water-soluble polymer in the raw material solution" means the amount of one type of water-soluble polymer selected from a cationic water-soluble polymer and a nonionic water-soluble polymer when the raw material solution contains one type of water-soluble polymer selected from a cationic water-soluble polymer and a nonionic water-soluble polymer, and means the total amount of the two or more types of water-soluble polymers when the raw material solution contains two or more types of water-soluble polymers selected from a cationic water-soluble polymer and a nonionic water-soluble polymer.
[0119] The cationic water-soluble polymer and the nonionic water-soluble polymer will be described below.
[0120] <Cationic water-soluble polymer> Cationic water-soluble polymers include water-soluble polymers that contain cationic groups but no anionic groups, as well as water-soluble polymers that contain both cationic and anionic groups and have an isoelectric point of 7 or greater.
[0121] The cationic water-soluble polymer may be a homopolymer or a copolymer.
[0122] The cationic group refers to a functional group that can be positively charged in the raw material solution. Examples of the cationic group include a quaternary ammonium group, a tertiary amino group, a secondary amino group, a primary amino group, a pyrrole group, a pyridyl group, a guanidinium group, a purine group, and a pyrimidine group.
[0123] A primary amino group has the formula: -NH 2 A secondary amino group has the formula: -NHR 1 A tertiary amino group is represented by the formula: -NR 1 R 2 A quaternary ammonium group is represented by the formula: -N + R 1 R 2 R 3 It is expressed as:
[0124] R 1 , R 2 and R 3are each independently, for example, an alkyl group which may have one or more substituents, a cycloalkyl group which may have one or more substituents, an alkenyl group which may have one or more substituents, a cycloalkenyl group which may have one or more substituents, an alkynyl group which may have one or more substituents, a cycloalkynyl group which may have one or more substituents, an aryl group which may have one or more substituents, an arylalkyl group which may have one or more substituents, an arylalkenyl group which may have one or more substituents, an arylalkynyl group which may have one or more substituents, an alkylaryl group which may have one or more substituents, an alkenylaryl group which may have one or more substituents, an alkynylaryl group which may have one or more substituents, etc. The explanations regarding the alkyl group, cycloalkyl group, alkenyl group, cycloalkenyl group, alkynyl group, cycloalkynyl group, aryl group, arylalkyl group, arylalkenyl group, arylalkynyl group, alkylaryl group, alkenylaryl group, and alkynylaryl group, as well as the explanations regarding one or more substituents, are as described above.
[0125] R 1 , R 2 and R 3 are each independently preferably an aliphatic hydrocarbon group, more preferably a saturated aliphatic hydrocarbon group. 1 , R 2 and R 3 are each independently preferably selected from an alkyl group which may have one or more substituents, a cycloalkyl group which may have one or more substituents, an alkenyl group which may have one or more substituents, a cycloalkenyl group which may have one or more substituents, an alkynyl group which may have one or more substituents and a cycloalkynyl group which may have one or more substituents, more preferably selected from an alkyl group which may have one or more substituents and a cycloalkyl group which may have one or more substituents, and even more preferably selected from an alkyl group which may have one or more substituents.
[0126] Examples of counter anions bonded to quaternary ammonium groups include alkyl sulfate ions, aryl sulfate ions, halide ions, sulfate ions, nitrate ions, nitrite ions, bicarbonate ions, carbonate ions, hydroxide ions, etc. Examples of alkyl sulfate ions include methyl sulfate ions, ethyl sulfate ions, propyl sulfate ions, butyl sulfate ions, etc. Examples of aryl sulfate ions include phenyl sulfate ions, etc.
[0127] The anionic group refers to a functional group that can be ionized in the raw material liquid and become negatively charged. Examples of the anionic group include a carboxyl group, a sulfo group, a phosphate group, and a phenol group.
[0128] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight-average molecular weight of the cationic water-soluble polymer is preferably 2000 or more, more preferably 4000 or more, and even more preferably 8000 or more. The upper limit can be appropriately adjusted, but is preferably 500000 or less, more preferably 200000 or less, and even more preferably 100000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0129] In one embodiment, the cationic water-soluble polymer can be selected from polyalkyleneimines.
[0130] Examples of polyalkyleneimines include polymers obtained by polymerizing one or more alkyleneamines by a conventional method. The polyalkyleneimine may be a polymer obtained by reacting a polymer obtained by polymerizing one or more alkyleneamines by a conventional method with a desired compound to chemically modify the polymer. The polyalkyleneimine may be linear or branched. Examples of polyalkyleneimines include polyethyleneimine, polypropyleneimine, polybutyleneimine, polypenteneimine, polyhexeneimine, etc.
[0131] The alkylene in the polyalkyleneimine may be linear or branched. The number of carbon atoms in the alkylene in the polyalkyleneimine is, for example, 2 to 6, preferably 2 to 4, and more preferably 2.
[0132] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the weight average molecular weight of the polyalkyleneimine is preferably 2000 or more, more preferably 4000 or more, and even more preferably 8000 or more. The upper limit can be appropriately adjusted, but is preferably 500000 or less, more preferably 200000 or less, and even more preferably 100000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0133] In another embodiment, the cationic water-soluble polymer has a repeating unit containing a carbon atom and one or more atoms having a higher electronegativity than the carbon atom (hereinafter referred to as "electronegative atoms"). The electronegative atoms can be selected from, for example, N, O, S, F, Cl, Br, I, etc., and are preferably selected from N and O.
[0134] The cationic water-soluble polymer having a repeating unit containing a carbon atom and one or more types of negative atoms may be a homopolymer or a copolymer, but is preferably a homopolymer.
[0135] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the weight-average molecular weight of the cationic water-soluble polymer having a repeating unit containing a carbon atom and one or more types of negative atoms is preferably 500 or more, more preferably 2000 or more, and even more preferably 10000 or more. The upper limit can be appropriately adjusted, but is preferably 500000 or less, more preferably 200000 or less, and even more preferably 100000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0136] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the molecular weight of the repeating unit containing a carbon atom and one or more kinds of negative atoms is preferably 20 or more, more preferably 30 or more, and even more preferably 45 or more. The upper limit can be appropriately adjusted, but is preferably 10,000 or less, more preferably 2,000 or less, and even more preferably 500 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0137] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the weight-average degree of polymerization of the repeating unit containing a carbon atom and one or more kinds of negative atoms is preferably 20 or more, more preferably 100 or more, and even more preferably 150 or more. The upper limit can be appropriately adjusted, but is preferably 200,000 or less, more preferably 100,000 or less, and even more preferably 60,000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0138] The larger the molecular weight of the repeating unit containing carbon atom and one or more kinds of negative atoms, the more the adsorption of the cationic water-soluble polymer to the surface of the aluminum compound particle is improved. Also, the larger the ratio of the number of carbon atoms to the number of negative atoms in the repeating unit containing carbon atom and one or more kinds of negative atoms, the more the adsorption of the cationic water-soluble polymer to the surface of the aluminum compound particle is improved. On the other hand, if the adsorption of the cationic water-soluble polymer to the surface of the aluminum compound particle is too high, the aluminum compound particles may aggregate with each other. Therefore, from the viewpoint of preventing the aggregation of the aluminum compound particles and improving the adsorption of the cationic water-soluble polymer to the surface of the aluminum compound particle, it is preferable to adjust the molecular weight of the repeating unit containing carbon atom and one or more kinds of negative atoms and the ratio of the number of carbon atoms to the number of negative atoms in the repeating unit.
[0139] When the molecular weight of a repeating unit containing a carbon atom and one or more kinds of electronegative atoms is 150 or less, the ratio of the number of carbon atoms to the number of electronegative atoms in the repeating unit is preferably 2 or more, more preferably 2.3 or more, and even more preferably 2.6 or more. The upper limit can be appropriately adjusted, but is preferably 10 or less, more preferably 8 or less, and even more preferably 5 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0140] When the molecular weight of a repeating unit containing a carbon atom and one or more kinds of electronegative atoms exceeds 150, the ratio of the number of carbon atoms to the number of electronegative atoms in the repeating unit is preferably 1 or more, more preferably 1.2 or more, and even more preferably 1.5 or more. The upper limit can be appropriately adjusted, but is preferably 10 or less, more preferably 8 or less, and even more preferably 5 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0141] The cationic water-soluble polymer preferably has a repeating unit containing a quaternary ammonium group. The quaternary ammonium group corresponds to the cationic group. The quaternary ammonium group is present in a side chain of the cationic water-soluble polymer.
[0142] The quaternary ammonium group is preferred from the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles with each other because of its bulkiness. The quaternary ammonium group is also preferred from the viewpoint of improving the adsorption of a cationic water-soluble polymer to the surface of the aluminum compound particles while preventing the aggregation of aluminum compound particles with each other.
[0143] The cationic water-soluble polymer having a repeating unit containing a quaternary ammonium group may be either a homopolymer or a copolymer, but is preferably a homopolymer.
[0144] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight-average molecular weight of the cationic water-soluble polymer having a repeating unit containing a quaternary ammonium group is preferably 10,000 or more, more preferably 20,000 or more, and even more preferably 40,000 or more. The upper limit can be appropriately adjusted, but is preferably 500,000 or less, more preferably 200,000 or less, and even more preferably 100,000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0145] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the molecular weight of the repeating unit containing a quaternary ammonium group is preferably 100 or more, more preferably 180 or more, and even more preferably 300 or more. The upper limit can be appropriately adjusted, but is preferably 10,000 or less, more preferably 2,000 or less, and even more preferably 500 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits. The "molecular weight of the repeating unit containing a quaternary ammonium group" is a value including the molecular weight of the counter anion bonded to the quaternary ammonium group.
[0146] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight-average degree of polymerization of the repeating unit containing a quaternary ammonium group is preferably 20 or more, more preferably 100 or more, and even more preferably 150 or more. The upper limit can be appropriately adjusted, but is preferably 3000 or less, more preferably 1100 or less, and even more preferably 550 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0147] The cationic water-soluble polymer having a repeating unit containing a quaternary ammonium group is preferably a water-soluble polymer represented by formula (I).
[0148] [ka]
[0149] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight-average molecular weight of the water-soluble polymer represented by formula (I) is preferably 10,000 or more, more preferably 20,000 or more, and even more preferably 40,000 or more. The upper limit can be appropriately adjusted, but is preferably 500,000 or less, more preferably 200,000 or less, and even more preferably 100,000 or less. Each of these upper limits may be combined with any of the above-mentioned upper limits.
[0150] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the molecular weight of the repeating unit in the water-soluble polymer represented by formula (I) is preferably 180 or more, more preferably 250 or more, and even more preferably 300 or more. The upper limit can be appropriately adjusted, but is preferably 5000 or less, more preferably 3000 or less, and even more preferably 1500 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0151] In formula (I), n represents the weight-average degree of polymerization of the repeating unit. From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, n is preferably 50 or more, more preferably 100 or more, and even more preferably 150 or more. The upper limit can be appropriately adjusted, but is preferably 5000 or less, more preferably 3000 or less, and even more preferably 1000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0152] In formula (I), R 1 ~R 4are each independently, for example, an alkyl group which may have one or more substituents, a cycloalkyl group which may have one or more substituents, an alkenyl group which may have one or more substituents, a cycloalkenyl group which may have one or more substituents, an alkynyl group which may have one or more substituents, a cycloalkynyl group which may have one or more substituents, an aryl group which may have one or more substituents, an arylalkyl group which may have one or more substituents, an arylalkenyl group which may have one or more substituents, an arylalkynyl group which may have one or more substituents, an alkylaryl group which may have one or more substituents, an alkenylaryl group which may have one or more substituents, an alkynylaryl group which may have one or more substituents, etc. The explanations regarding the alkyl group, cycloalkyl group, alkenyl group, cycloalkenyl group, alkynyl group, cycloalkynyl group, aryl group, arylalkyl group, arylalkenyl group, arylalkynyl group, alkylaryl group, alkenylaryl group, and alkynylaryl group, as well as the explanations regarding one or more substituents, are as described above.
[0153] R 1 , R 2 , R 3 and R 4 are each independently preferably an aliphatic hydrocarbon group, more preferably a saturated aliphatic hydrocarbon group. 1 , R 2 , R 3 and R 4 are each independently preferably selected from an alkyl group which may have one or more substituents, a cycloalkyl group which may have one or more substituents, an alkenyl group which may have one or more substituents, a cycloalkenyl group which may have one or more substituents, an alkynyl group which may have one or more substituents and a cycloalkynyl group which may have one or more substituents, more preferably selected from an alkyl group which may have one or more substituents and a cycloalkyl group which may have one or more substituents, and even more preferably selected from an alkyl group which may have one or more substituents.
[0154] Considering the water solubility of the water-soluble polymer represented by formula (I) and the adsorptivity to the surface of aluminum compound particles, the molecular weight of the aliphatic hydrocarbon group is preferably 60 or less, more preferably 50 or less, and even more preferably 40 or less. The lower limit can be appropriately selected, but is preferably 15 or more. This lower limit may be combined with any of the above upper limits.
[0155] In formula (I), L is -CO-, -O-CO-, -CO-O-, -NH-CO-, -CO-NH-, -O- or -CH 2 - The left side of L is R 4 is attached to the carbon atom to which L is attached, and the right side of L is -(CH 2 ) p - is bonded to.
[0156] L is preferably -CO-O-.
[0157] In formula (I), p represents an integer of 1 to 3.
[0158] p is preferably 2 to 3, and more preferably 2.
[0159] In the cationic water-soluble polymer represented by formula (I), a counter anion is bonded to the quaternary ammonium group. In formula (I), the counter anion is represented by the formula: (X q- ) 1 / q The formula is represented by the formula: where q represents an integer of 1 to 3. q is preferably 1 to 2, and more preferably 1.
[0160] Considering the water solubility of the water-soluble polymer represented by formula (I) and the adsorptivity to the surface of aluminum compound particles, the molecular weight of the counter anion is preferably 300 or less, more preferably 200 or less, and even more preferably 150 or less. The lower limit can be appropriately adjusted, but is preferably 15. This lower limit may be combined with any of the above-mentioned upper limits.
[0161] Examples of the counter anion include an alkyl sulfate ion, an aryl sulfate ion, a halide ion, a sulfate ion, a nitrate ion, a nitrite ion, a hydrogen carbonate ion, a carbonate ion, and a hydroxide ion.
[0162] Alkyl sulfate ions have the formula: RO-SO 3 - [wherein R represents an alkyl group which may have one or more substituents.] The alkyl group and the one or more substituents are as described above. Examples of alkyl sulfate ions include methyl sulfate ion, ethyl sulfate ion, propyl sulfate ion, and butyl sulfate ion.
[0163] An example of the aryl sulfate ion is a phenyl sulfate ion.
[0164] An example of the cationic water-soluble polymer represented by formula (I) is poly[2-(ethyldimethylammonio)ethyl methacrylate]] ethyl sulfate. Poly[2-(ethyldimethylammonio)ethyl methacrylate]] ethyl sulfate is represented by the following formula. In the following formula, "Et" represents an ethyl group.
[0165] [ka]
[0166] <Nonionic water-soluble polymer> The nonionic water-soluble polymer means a water-soluble polymer that does not contain any cationic group or anionic group. The cationic group and the anionic group are as described above.
[0167] The nonionic water-soluble polymer may be a homopolymer or a copolymer.
[0168] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight-average molecular weight of the nonionic water-soluble polymer is preferably 500 or more, more preferably 1000 or more, and even more preferably 2000 or more. The upper limit can be appropriately adjusted, but is preferably 500000 or less, more preferably 200000 or less, and even more preferably 100000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0169] In one embodiment, the nonionic water-soluble polymer has a repeating unit containing a carbon atom and one or more types of atoms having a higher electronegativity than the carbon atom (hereinafter referred to as "electronegative atoms"). The electronegative atoms can be selected from, for example, N, O, S, F, Cl, Br, I, etc., and are preferably selected from N and O.
[0170] The nonionic water-soluble polymer having a repeating unit containing a carbon atom and one or more electronegative atoms may be a homopolymer or a copolymer, but is preferably a homopolymer.
[0171] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight-average molecular weight of the nonionic water-soluble polymer having a repeating unit containing a carbon atom and one or more types of negative atoms is preferably 500 or more, more preferably 2000 or more, and even more preferably 10000 or more. The upper limit can be appropriately adjusted, but is preferably 500000 or less, more preferably 200000 or less, and even more preferably 100000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0172] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the molecular weight of the repeating unit containing a carbon atom and one or more kinds of negative atoms is preferably 20 or more, more preferably 30 or more, and even more preferably 45 or more. The upper limit can be appropriately adjusted, but is preferably 10,000 or less, more preferably 2,000 or less, and even more preferably 500 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0173] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the weight-average degree of polymerization of the repeating unit containing a carbon atom and one or more kinds of negative atoms is preferably 20 or more, more preferably 100 or more, and even more preferably 150 or more. The upper limit can be appropriately adjusted, but is preferably 200,000 or less, more preferably 100,000 or less, and even more preferably 60,000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0174] The larger the molecular weight of the repeating unit containing carbon atom and one or more kinds of negative atoms, the more the adsorption of the nonionic water-soluble polymer to the surface of the aluminum compound particle is improved. Also, the larger the ratio of the number of carbon atoms to the number of negative atoms in the repeating unit containing carbon atom and one or more kinds of negative atoms, the more the adsorption of the nonionic water-soluble polymer to the surface of the aluminum compound particle is improved. On the other hand, if the adsorption of the nonionic water-soluble polymer to the surface of the aluminum compound particle is too high, the aluminum compound particles may aggregate together. Therefore, from the viewpoint of preventing the aggregation of the aluminum compound particles and improving the adsorption of the nonionic water-soluble polymer to the surface of the aluminum compound particle, it is preferable to adjust the molecular weight of the repeating unit containing carbon atom and one or more kinds of negative atoms and the ratio of the number of carbon atoms to the number of negative atoms in the repeating unit.
[0175] When the molecular weight of a repeating unit containing a carbon atom and one or more kinds of electronegative atoms is 150 or less, the ratio of the number of carbon atoms to the number of electronegative atoms in the repeating unit is preferably 2 or more, more preferably 2.3 or more, and even more preferably 2.6 or more. The upper limit can be appropriately adjusted, but is preferably 10 or less, more preferably 8 or less, and even more preferably 5 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0176] When the molecular weight of a repeating unit containing a carbon atom and one or more kinds of electronegative atoms exceeds 150, the ratio of the number of carbon atoms to the number of electronegative atoms in the repeating unit is preferably 1 or more, more preferably 1.2 or more, and even more preferably 1.5 or more. The upper limit can be appropriately adjusted, but is preferably 10 or less, more preferably 8 or less, and even more preferably 5 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0177] In another embodiment, the non-ionic water-soluble polymer may be selected from cellulose derivatives, such as cellulose ethers.
[0178] Cellulose ethers are compounds in which the hydroxyl groups of cellulose are converted to ethers. Examples of cellulose ethers include alkyl celluloses, hydroxyalkyl celluloses, and hydroxyalkyl alkyl celluloses.
[0179] The alkyl in the alkyl cellulose, hydroxyalkyl cellulose, and hydroxyalkyl alkyl cellulose may be linear or branched, and the number of carbon atoms in the alkyl cellulose, hydroxyalkyl cellulose, and hydroxyalkyl alkyl cellulose is, for example, 1 to 16, preferably 1 to 12, more preferably 1 to 8, even more preferably 1 to 6, and even more preferably 1 to 3.
[0180] Examples of the alkyl cellulose include methyl cellulose, ethyl cellulose, propyl cellulose, butyl cellulose, pentyl cellulose, and hexyl cellulose.
[0181] Examples of hydroxyalkyl cellulose include hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxybutyl cellulose, hydroxypentyl cellulose, and hydroxyhexyl cellulose.
[0182] Hydroxyalkyl alkyl cellulose is a cellulose having both a hydroxyalkyl group and an alkyl group, and examples thereof include hydroxymethyl methyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, and hydroxybutyl methyl cellulose.
[0183] Among the cellulose ethers, hydroxyalkyl alkyl cellulose is preferred, and hydroxypropyl methyl cellulose is more preferred. The molecular formula of the repeating unit in hydroxypropyl methyl cellulose is, for example, C x H y O z (wherein, x is 6 or more and 10 or less, y is 10 or more and 20 or less, and z is 5 or more and 7 or less).
[0184] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the weight-average molecular weight of the cellulose ether is preferably 2000 or more, more preferably 5000 or more, and even more preferably 30000 or more. The upper limit can be appropriately adjusted, but is preferably 500000 or less, more preferably 200000 or less, and even more preferably 100000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0185] In yet another embodiment, the non-ionic water-soluble polymer may be selected from polyvinylpyrrolidone.
[0186] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight average molecular weight of polyvinylpyrrolidone is preferably 1000 or more, more preferably 3000 or more, and even more preferably 8000 or more. The upper limit can be appropriately adjusted, but is preferably 1000000 or less, more preferably 400000 or less, and even more preferably 200000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0187] In yet another embodiment, the non-ionic water-soluble polymer may be selected from poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) represented by the following formula (II):
[0188] [ka]
[0189] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight-average molecular weight of the water-soluble polymer represented by formula (II) is preferably 500 or more, more preferably 1000 or more, and even more preferably 2000 or more. The upper limit can be appropriately adjusted, but is preferably 100000 or less, more preferably 50000 or less, and even more preferably 30000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0190] In formula (II), x, y and z represent the weight average degrees of polymerization of the left, center and right repeating units, respectively.
[0191] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the ratio of x to y is preferably 0.10 or more and 5.00 or less, more preferably 0.15 or more and 2.00 or less, and even more preferably 0.20 or more and 1.60 or less.
[0192] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the ratio of z to y is preferably 0.10 or more and 5.00 or less, more preferably 0.15 or more and 2.00 or less, and even more preferably 0.20 or more and 1.60 or less.
[0193] Engineering (1b) Step (1b) is a step of adding a precipitating agent to the raw material liquid prepared in step (1a) to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal.
[0194] The raw material liquid prepared in step (1a) contains metal ions generated by ionization of the water-soluble salt. The precipitant added to the raw material liquid causes at least a portion of the metal ions generated by ionization of the water-soluble salt to precipitate as a poorly water-soluble salt, and can be appropriately selected depending on the type of water-soluble salt contained in the raw material liquid, the type of poorly water-soluble salt to be precipitated, etc.
[0195] When the raw material liquid contains a water-soluble cerium salt, a precipitant that precipitates cerium ions as a poorly water-soluble cerium salt can be used. The poorly water-soluble cerium salt to be precipitated can be selected from, for example, cerium hydroxide, cerium carbonate, etc., and is preferably cerium hydroxide. When the poorly water-soluble cerium salt to be precipitated is cerium carbonate, the carbonate ions used to form cerium carbonate may inhibit the formation of a precipitate of zirconium ions. For example, the carbonate ions may cause a water-soluble zirconium complex (e.g., [Zr(CO 3 ) 4 ] 4- [ZrOH(CO 3 ) 3 ] 3- etc.) may be formed.
[0196] When the raw material liquid contains a water-soluble zirconium salt, a precipitant that precipitates zirconium ions as a poorly water-soluble zirconium salt can be used. The poorly water-soluble zirconium salt to be precipitated can be selected from, for example, zirconium hydroxide, basic zirconium sulfate, etc., but is preferably selected from zirconium hydroxide and basic zirconium sulfate, and more preferably zirconium hydroxide.
[0197] When the raw material liquid contains a water-soluble rare earth metal salt, a precipitant that precipitates rare earth metal ions as poorly water-soluble rare earth metal salts can be used. The poorly water-soluble rare earth metal salts to be precipitated can be selected from, for example, hydroxides and carbonates of rare earth metal elements, but are preferably hydroxides of rare earth metal elements (e.g., lanthanum hydroxide, neodymium hydroxide, yttrium hydroxide, etc.). When the poorly water-soluble rare earth metal salt to be precipitated is a carbonate of a rare earth metal element, the carbonate ions used for forming the carbonate may inhibit the formation of a precipitate of zirconium ions.
[0198] One type of precipitant may precipitate two or more types of metal ions as poorly water-soluble metal salts. Thus, the precipitant that precipitates cerium ions as poorly water-soluble cerium salts, the precipitant that precipitates zirconium ions as poorly water-soluble zirconium salts, and the precipitant that precipitates rare earth metal ions as poorly water-soluble rare earth metal salts may be the same or different.
[0199] The precipitant may be selected from, for example, an aqueous solution containing sulfate ions and a compound capable of dissolving in water to generate sulfate ions. This precipitant can precipitate zirconium ions as basic zirconium sulfate. The aqueous solution containing sulfate ions can be obtained by dissolving a compound capable of dissolving in water to generate sulfate ions in water. The compound capable of dissolving in water to generate sulfate ions may be selected from, for example, ammonium sulfate, sulfuric acid, an alkali metal sulfate, cerium (III) sulfate, a rare earth metal sulfate, and the like. From the viewpoint of increasing the uniformity of the solid solution phase (for example, a solid solution phase of cerium oxide and zirconium oxide) formed by the cerium element, the zirconium element, and the oxygen element, and from the viewpoint of easy availability, it is preferable to select from ammonium sulfate, sulfuric acid, and an alkali metal sulfate. The rare earth metal sulfate is preferably a trivalent rare earth metal sulfate.
[0200] The precipitant may be selected from an aqueous solution containing hydroxide ions and a compound capable of dissolving in water to generate hydroxide ions. The precipitant can precipitate cerium ions, zirconium ions, and rare earth metal ions as cerium hydroxide, zirconium hydroxide, and hydroxides of rare earth metal elements, respectively. The aqueous solution containing hydroxide ions can be obtained by dissolving a compound capable of dissolving in water to generate hydroxide ions in water. The compound capable of dissolving in water to generate hydroxide ions may be selected from, for example, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, lithium hydroxide, ammonia, amines, quaternary ammonium hydroxide, guanidine, alkali metal carbonates, alkali metal bicarbonates, urea, etc., but is preferably selected from sodium hydroxide and ammonia.
[0201] The pH of the raw material liquid (raw material liquid after adding the precipitant) when forming the precipitate can be appropriately adjusted. From the viewpoint of suppressing the elution of components in the precipitate including cerium element, zirconium element, aluminum element, and occasionally rare earth metal element, the pH can be set to, for example, 9 or more and 14 or less.
[0202] By adding a precipitating agent to the raw material liquid prepared in step (1a), a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal is formed.
[0203] The cerium element is contained in the precipitate in the form of a poorly water-soluble cerium salt. The poorly water-soluble cerium salt contained in the precipitate may be a poorly water-soluble cerium salt contained in the raw material liquid from the beginning, or may be a poorly water-soluble cerium salt formed by a precipitant. However, from the viewpoint of improving the dispersibility of the aluminum compound particles in the precipitate formed in step (1b) and the cake obtained in step (1c), and thereby improving the OSC of the composite oxide produced in step (1d), it is preferable that the poorly water-soluble cerium salt is a poorly water-soluble cerium salt formed by a precipitant.
[0204] The zirconium element is contained in the precipitate in the form of a poorly water-soluble zirconium salt. The poorly water-soluble zirconium salt contained in the precipitate may be a poorly water-soluble zirconium salt contained in the raw material liquid from the beginning, or may be a poorly water-soluble zirconium salt formed by a precipitating agent. However, from the viewpoint of improving the dispersibility of the aluminum compound particles in the precipitate formed in step (1b) and the cake obtained in step (1c), and thus improving the OSC of the composite oxide produced in step (1d), it is preferable that the poorly water-soluble zirconium salt is a poorly water-soluble zirconium salt formed by a precipitating agent.
[0205] The rare earth metal element is contained in the precipitate in the form of a poorly water-soluble rare earth metal salt. The poorly water-soluble rare earth metal salt contained in the precipitate may be a poorly water-soluble rare earth metal salt contained in the raw material liquid from the beginning, or may be a poorly water-soluble rare earth metal salt formed by a precipitant. However, from the viewpoint of improving the dispersibility of the aluminum compound particles in the precipitate formed in step (1b) and the cake obtained in step (1c), and thus improving the OSC of the composite oxide produced in step (1d), the poorly water-soluble rare earth metal salt formed by a precipitant is preferable.
[0206] The precipitate obtained in step (1b) contains poorly water-soluble salt particles and aluminum compound particles in a mixed state. Examples of poorly water-soluble salt particles include composite salt particles containing a poorly water-soluble cerium salt, a poorly water-soluble zirconium salt, and optionally a poorly water-soluble rare earth metal salt, poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles, etc. From the viewpoint of improving the OSC of the composite oxide produced in step (1d), it is preferable that the precipitate contains composite salt particles. The precipitate may contain poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles, etc. in addition to the composite salt particles.
[0207] The water-soluble polymer adsorbed on the surface of the aluminum compound particles (preferably a water-soluble polymer layer formed on the surface of the aluminum compound particles) effectively suppresses aggregation of the aluminum compound particles, thereby improving the dispersibility of the aluminum compound particles in the precipitate formed in step (1b).
[0208] In the precipitate formed in step (1b), the poorly water-soluble salt particles are separated by aluminum compound particles and water-soluble polymers (preferably water-soluble polymer layers formed on the surfaces of the aluminum compound particles) adsorbed on the surfaces of the aluminum compound particles, which effectively suppresses contact between the poorly water-soluble salt particles. The above-mentioned improvement in dispersibility of the aluminum compound particles also contributes to the suppression of contact between the poorly water-soluble salt particles.
[0209] Engineering (1c) The step (1c) is a step of separating the precipitate from the raw material liquid subjected to the step (1b) to obtain a cake containing the precipitate.
[0210] The cake can be obtained by subjecting the raw material liquid subjected to step (1b) to a solid-liquid separation method. The solid-liquid separation method can be selected from, for example, filtration, centrifugation, decantation, etc., but filtration is preferred from the viewpoints of ease of operation and excellent solid-liquid separation efficiency. Since the solvent is not completely removed, the solvent remains in the cake. The cake differs from a dried solid in that it is an undried solid.
[0211] The cake obtained in step (1c) contains poorly water-soluble salt particles and aluminum compound particles in a mixed state. Examples of poorly water-soluble salt particles include composite salt particles containing poorly water-soluble cerium salt, poorly water-soluble zirconium salt, and optionally poorly water-soluble rare earth metal salt, poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles, etc. From the viewpoint of improving the OSC of the composite oxide produced in step (1d), it is preferable that the cake contains composite salt particles. In addition to the composite salt particles, the cake may contain poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles, etc.
[0212] The water-soluble polymer adsorbed on the surface of the aluminum compound particles (preferably a water-soluble polymer layer formed on the surface of the aluminum compound particles) effectively suppresses aggregation of the aluminum compound particles, thereby improving the dispersibility of the aluminum compound particles in the cake obtained in step (1c).
[0213] In the cake obtained in step (1c), the poorly water-soluble salt particles are separated by aluminum compound particles and water-soluble polymers (preferably water-soluble polymer layers formed on the surfaces of the aluminum compound particles) adsorbed on the surfaces of the aluminum compound particles, which effectively suppresses contact between the poorly water-soluble salt particles. The above-mentioned improvement in dispersibility of the aluminum compound particles also contributes to the suppression of contact between the poorly water-soluble salt particles.
[0214] The cake obtained in step (1c) is preferably washed with a washing liquid before being subjected to step (1d). As the washing liquid, water (e.g., pure water such as ion-exchanged water) can be used. In addition, from the viewpoint of suppressing the elution of components in the precipitate and from the viewpoint of washing and removing sulfur content in the precipitate, a solution containing a sodium salt (sodium hydroxide, sodium carbonate, sodium bicarbonate, etc.), ammonia water, or a solution containing an acid (nitric acid, acetic acid, etc.) can be used as the washing liquid, and the pH of the washing liquid can be adjusted to, for example, 6 to 14.
[0215] Engineering (1d) Step (1d) is a step of calcining the cake obtained in step (1c) to produce a composite oxide containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal.
[0216] In the cake obtained in step (1c), between the poorly water-soluble salt particles, there are aluminum compound particles and a water-soluble polymer adsorbed on the surface of the aluminum compound particles (preferably a water-soluble polymer layer formed on the surface of the aluminum compound particles), which effectively suppresses contact between the poorly water-soluble salt particles. By effectively suppressing contact between the poorly water-soluble salt particles, sintering between the poorly water-soluble salt particles is effectively suppressed when the cake is baked in step (1d), and a decrease in the specific surface area of the complex oxide caused by the sintering between the poorly water-soluble salt particles and a decrease in the OSC of the complex oxide caused by the decrease in the specific surface area of the complex oxide are effectively suppressed. Therefore, in step (1d), a complex oxide with improved OSC can be produced. The complex oxide produced in step (1d) is preferably the complex oxide of the present invention.
[0217] The precipitate can be calcined according to a conventional method. Calcination is usually carried out under air. The calcination temperature is usually 400°C to 1200°C, preferably 500°C to 1100°C, more preferably 600°C to 1000°C. The calcination time is usually 0.1 hours to 20 hours, preferably 0.5 hours to 10 hours, more preferably 1 hour to 5 hours.
[0218] The obtained composite oxide may be pulverized as necessary. The pulverization can be carried out according to a conventional method. For example, the pulverization can be carried out in a dry or wet manner using a mortar, a hammer mill, a ball mill, a bead mill, a jet mill, a roller mill, or the like.
[0219] Hereinafter, an embodiment of the first manufacturing method will be described.
[0220] <Embodiment 1A> In embodiment 1A, in step (1a), a raw material solution is prepared in which the cerium salt, the zirconium salt, and the rare earth metal salt are all water-soluble salts. Embodiment 1A also includes an embodiment in which the raw material solution prepared in step (1a) does not contain a rare earth metal salt. In an embodiment in which the raw material solution prepared in step (1a) does not contain a rare earth metal salt, "the cerium salt, the zirconium salt, and the rare earth metal salt are all water-soluble salts" means that the cerium salt and the zirconium salt are both water-soluble salts.
[0221] In embodiment 1A, in step (1b), a precipitant that precipitates cerium ions as a poorly water-soluble cerium salt and a precipitant that precipitates zirconium ions as a poorly water-soluble zirconium salt are used as precipitants added to the raw material solution. In an embodiment in which the raw material solution contains a rare earth metal salt, a precipitant that precipitates rare earth metal ions as a poorly water-soluble rare earth metal salt is also used. These precipitants may be the same type or different types.
[0222] Embodiment 1A encompasses Embodiment 1A-1 and Embodiment 1A-2.
[0223] <Embodiment 1A-1> Hereinafter, embodiment 1A-1 will be described.
[0224] In embodiment 1A-1, in step (1b), a first precipitant selected from an aqueous solution containing sulfate ions and a compound that can be dissolved in water to produce sulfate ions is added to the raw material liquid to form a first precipitate containing zirconium element and aluminum element, and then a second precipitant selected from an aqueous solution containing hydroxide ions and a compound that can be dissolved in water to produce hydroxide ions is added to the raw material liquid to form a second precipitate containing cerium element, zirconium element, aluminum element, and optionally a rare earth metal element.
[0225] In step (1b), when a first precipitating agent is added to the raw material liquid, a first precipitate containing elemental zirconium and elemental aluminum is formed.
[0226] The zirconium element is contained in the first precipitate in the form of basic zirconium sulfate, which is a poorly water-soluble zirconium salt formed by the first precipitating agent.
[0227] The aluminum element is contained in the first precipitate in the form of aluminum compound particles. The aluminum compound particles originate from the aluminum compound particles originally contained in the raw material liquid. The aluminum compound particles in the raw material liquid are coprecipitated with the poorly water-soluble zirconium salt formed by the first precipitant.
[0228] The first precipitate contains basic zirconium sulfate particles and aluminum compound particles in a mixture.
[0229] From the viewpoint of sufficiently precipitating basic zirconium sulfate and improving the OSC of the composite oxide produced in step (1d), the temperature of the raw material liquid when the first precipitant is added is preferably 40°C or more and 150°C or less, more preferably 55°C or more and 130°C or less, and even more preferably 70°C or more and 100°C or less.
[0230] From the viewpoints of sufficiently precipitating basic zirconium sulfate, suppressing the adverse effects of excess sulfate ions, and improving the OSC of the composite oxide produced in step (1d), it is preferable to add the first precipitant to the raw material liquid so that the molar amount of sulfate ions in the raw material liquid is 0.10 to 10 times the molar amount of zirconium element in the raw material liquid. The molar amount of sulfate ions in the raw material liquid is more preferably 0.20 to 5.0 times, and even more preferably 0.30 to 2.0 times, the molar amount of zirconium element in the raw material liquid.
[0231] From the viewpoint of sufficiently precipitating basic zirconium sulfate and improving the OSC of the composite oxide produced in step (1d), it is preferable to age the first precipitate while stirring the raw material liquid after adding the first precipitant. The ageing time is preferably 0.1 hours or more and 10 hours or less, more preferably 0.2 hours or more and 5 hours or less, and even more preferably 0.3 hours or more and 3 hours or less.
[0232] After the first precipitate is formed and aged as necessary, a second precipitating agent is added to the raw material liquid to form a second precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element.
[0233] The cerium element is contained in the second precipitate in the form of cerium hydroxide, which is a poorly water-soluble cerium salt formed by the second precipitating agent.
[0234] The zirconium element is contained in the second precipitate in the form of zirconium hydroxide. Zirconium hydroxide is a poorly water-soluble zirconium salt formed by the second precipitating agent. The basic zirconium sulfate formed by the first precipitating agent is converted to zirconium hydroxide by the second precipitating agent.
[0235] The rare earth metal element is contained in the second precipitate in the form of a hydroxide of the rare earth metal element. The hydroxide of the rare earth metal element is a poorly water-soluble rare earth metal salt formed by the second precipitating agent. The poorly water-soluble rare earth metal salt formed by the second precipitating agent is coprecipitated with the poorly water-soluble cerium salt formed by the second precipitating agent.
[0236] The aluminum element is contained in the second precipitate in the form of aluminum compound particles. The aluminum compound particles originate from the aluminum compound particles originally contained in the raw material liquid. The aluminum compound particles in the raw material liquid are coprecipitated with the poorly water-soluble cerium salt formed by the second precipitating agent and, in some cases, the poorly water-soluble rare earth metal salt formed by the second precipitating agent. At least a portion of the aluminum compound particles contained in the first precipitate is usually contained as it is in the second precipitate.
[0237] The second precipitate contains composite salt particles containing cerium hydroxide, zirconium hydroxide, and optionally hydroxides of rare earth metal elements other than cerium hydroxide, and aluminum compound particles in a mixed state. The second precipitate may contain cerium hydroxide particles, zirconium hydroxide particles, hydroxide particles of rare earth metal elements, etc., in addition to the composite salt particles. The composite salt particles are formed, for example, by adhesion and growth of cerium hydroxide and / or hydroxides of rare earth metal elements other than cerium hydroxide formed by the second precipitating agent on the surface of basic zirconium sulfate formed by the first precipitating agent (the basic zirconium sulfate is converted to zirconium hydroxide by the second precipitating agent).
[0238] From the viewpoints of sufficiently precipitating the target hydroxides (cerium hydroxide, zirconium hydroxide, and optionally hydroxides of rare earth metal elements) while preventing dissolution of the aluminum compound particles by hydroxide ions and improving the OSC of the composite oxide produced in step (1d), the temperature of the raw material liquid when the second precipitant is added is preferably 35°C or more and 60°C or less, more preferably 35°C or more and 55°C or less, and even more preferably 35°C or more and 45°C or less.
[0239] From the viewpoint of suppressing dissolution of the aluminum compound particles by hydroxide ions and improving the OSC of the composite oxide produced in step (1d), it is preferable to add the second precipitant to the raw material liquid so that the molar amount of hydroxide ions in the raw material liquid is 2.0 to 10 times the molar amount of oxygen required to convert the cerium element, zirconium element, and rare earth metal element in the raw material liquid into oxides. The molar amount of hydroxide ions in the raw material liquid is more preferably 2.0 to 5.0 times, and even more preferably 2.0 to 3.0 times, the molar amount of oxygen required to convert the cerium element, zirconium element, and rare earth metal element in the raw material liquid into oxides.
[0240] The molar amount (M) of oxygen required to convert the cerium, zirconium, and rare earth metal elements in the raw material solution into their oxides can be calculated by M = [(molar amount of cerium) × 2] + [(molar amount of zirconium) × 2] + [(molar amount of rare earth metal elements other than cerium, praseodymium, and terbium) × 3 / 2] + [(molar amount of praseodymium) × 11 / 6] + [(molar amount of terbium) × 7 / 4].
[0241] From the viewpoint of sufficiently precipitating the target hydroxides (cerium hydroxide, zirconium hydroxide, and optionally hydroxides of rare earth metal elements) and improving the OSC of the composite oxide produced in step (1d), it is preferable to age the second precipitate while stirring the raw material liquid after adding the second precipitant. The ageing time is preferably 1 hour or more and 96 hours or less, more preferably 1 hour or more and 48 hours or less, and even more preferably 1 hour or more and 24 hours or less.
[0242] In embodiment 1A-1, in step (1c), it is preferable to separate the second precipitate from the raw material liquid subjected to step (1b) to obtain a cake containing the second precipitate.
[0243] In embodiment 1A-1, in step (1d), it is preferable to calcinate the cake containing the second precipitate obtained in step (1c) to produce a composite oxide containing cerium, zirconium, aluminum, and optionally a rare earth metal element.
[0244] <Embodiment 1A-2> Hereinafter, embodiment 1A-2 will be described.
[0245] In embodiment 1A-2, in step (1b), a precipitant selected from an aqueous solution containing hydroxide ions and a compound that can be dissolved in water to generate hydroxide ions is added to the raw material liquid to form a precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element. In embodiment 1A-2, it is not necessary to use a precipitant selected from an aqueous solution containing sulfate ions and a compound that can be dissolved in water to generate sulfate ions.
[0246] When a precipitating agent is added to the raw material liquid, a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal is formed.
[0247] The cerium element is present in the precipitate in the form of cerium hydroxide, a sparingly water-soluble cerium salt formed by the precipitating agent.
[0248] The zirconium element is contained in the precipitate in the form of zirconium hydroxide. The zirconium hydroxide is a poorly water-soluble zirconium salt formed by the precipitating agent. The poorly water-soluble zirconium salt formed by the precipitating agent is coprecipitated with the poorly water-soluble cerium salt formed by the precipitating agent.
[0249] The rare earth metal element is contained in the precipitate in the form of a hydroxide of the rare earth metal element. The hydroxide of the rare earth metal element is a poorly water-soluble rare earth metal salt formed by the precipitating agent. The poorly water-soluble rare earth metal salt formed by the precipitating agent is coprecipitated with the poorly water-soluble cerium salt and the poorly water-soluble zirconium salt formed by the precipitating agent.
[0250] The aluminum element is contained in the precipitate in the form of aluminum compound particles. The aluminum compound particles originate from the aluminum compound particles originally contained in the raw material liquid. The aluminum compound particles in the raw material liquid are coprecipitated with the poorly water-soluble cerium salt formed by the precipitant, the poorly water-soluble zirconium salt, and optionally the poorly water-soluble rare earth metal salt formed by the precipitant.
[0251] The precipitate contains composite salt particles containing cerium hydroxide, zirconium hydroxide, and optionally a hydroxide of a rare earth metal element other than cerium hydroxide, and aluminum compound particles in a mixed state. The precipitate may contain cerium hydroxide particles, zirconium hydroxide particles, hydroxide particles of a rare earth metal element, etc. in addition to the composite salt particles.
[0252] The above description regarding the temperature of the raw material liquid when the second precipitant is added in embodiment 1A-1 also applies to the temperature of the raw material liquid when the precipitant is added in embodiment 1A-2.
[0253] The above description regarding the amount of the second precipitant added to the raw material liquid in embodiment 1A-1 (the above description regarding the molar amount of hydroxide ions in the raw material liquid) also applies to the amount of the precipitant added to the raw material liquid in embodiment 1A-2 (the molar amount of hydroxide ions in the raw material liquid).
[0254] From the viewpoint of sufficiently precipitating the target hydroxides (cerium hydroxide, zirconium hydroxide, and optionally hydroxides of rare earth metal elements) and improving the OSC of the composite oxide produced in step (1d), it is preferable to age the precipitate while stirring the raw material liquid after adding the precipitant. The ageing time is preferably 1 hour or more and 96 hours or less, more preferably 1 hour or more and 48.0 hours or less, and even more preferably 1 hour or more and 24 hours or less.
[0255] <Embodiment 1B> In embodiment 1B, in step (1a), a raw material liquid is prepared in which the cerium salt and the rare earth metal salt are both water-soluble salts, and the zirconium salt is a poorly water-soluble salt. Embodiment 1B also includes an embodiment in which the raw material liquid prepared in step (1a) does not contain a rare earth metal salt. In an embodiment in which the raw material liquid prepared in step (1a) does not contain a rare earth metal salt, "both the cerium salt and the rare earth metal salt are water-soluble salts, and the zirconium salt is a poorly water-soluble salt" means that the cerium salt is a water-soluble salt and the zirconium salt is a poorly water-soluble salt.
[0256] In embodiment 1B, a precipitant that precipitates cerium ions as poorly water-soluble cerium salts is used as the precipitant added to the raw material solution in step (1b). In an embodiment in which the raw material solution contains a rare earth metal salt, a precipitant that precipitates rare earth metal ions as poorly water-soluble rare earth metal salts is also used. These precipitants may be the same type or different types.
[0257] In embodiment 1B, in step (1b), it is preferable to add a precipitant selected from an aqueous solution containing hydroxide ions and a compound that can be dissolved in water to generate hydroxide ions to the raw material liquid to form a precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element. In embodiment 1B, it is not necessary to use a precipitant selected from an aqueous solution containing sulfate ions and a compound that can be dissolved in water to generate sulfate ions.
[0258] When a precipitating agent is added to the raw material liquid, a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal is formed.
[0259] The cerium element is present in the precipitate in the form of cerium hydroxide, a sparingly water-soluble cerium salt formed by the precipitating agent.
[0260] The zirconium element is contained in the precipitate in the form of a poorly water-soluble salt contained in the raw material liquid from the beginning, or in the form of zirconium hydroxide. When the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is basic zirconium sulfate, the basic zirconium sulfate is converted to zirconium hydroxide by the precipitating agent. In this case, the zirconium element is contained in the precipitate in the form of zirconium hydroxide. When the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is zirconium hydroxide, the zirconium element is contained in the precipitate in the form of a poorly water-soluble salt (zirconium hydroxide) contained in the raw material liquid from the beginning.
[0261] The rare earth metal element is contained in the precipitate in the form of a hydroxide of the rare earth metal element. The hydroxide of the rare earth metal element is a poorly water-soluble rare earth metal salt formed by the precipitating agent. The poorly water-soluble rare earth metal salt formed by the precipitating agent is coprecipitated with the poorly water-soluble cerium salt formed by the precipitating agent.
[0262] The aluminum element is contained in the precipitate in the form of aluminum compound particles. The aluminum compound particles originate from the aluminum compound particles originally contained in the raw material liquid. The aluminum compound particles in the raw material liquid are coprecipitated with the poorly water-soluble cerium salt formed by the precipitant and, in some cases, the poorly water-soluble rare earth metal salt formed by the precipitant.
[0263] The precipitate contains composite salt particles containing cerium hydroxide, poorly water-soluble zirconium salt (when the poorly water-soluble zirconium salt contained in the raw material solution from the beginning is basic zirconium sulfate, basic zirconium sulfate is converted to zirconium hydroxide by the precipitant), and optionally hydroxide of a rare earth metal element other than cerium hydroxide, and aluminum compound particles in a mixed state. In addition to the composite salt particles, the precipitate may contain cerium hydroxide particles, poorly water-soluble zirconium salt particles, zirconium hydroxide particles, hydroxide particles of a rare earth metal element, etc. The composite salt particles are formed, for example, by the adhesion and growth of cerium hydroxide and / or hydroxide of a rare earth metal element other than cerium hydroxide formed by the precipitant on the surface of poorly water-soluble zirconium salt (when the poorly water-soluble zirconium salt contained in the raw material solution from the beginning is basic zirconium sulfate, basic zirconium sulfate is converted to zirconium hydroxide by the precipitant).
[0264] The above description regarding the temperature of the raw material liquid when the second precipitating agent is added in embodiment 1A-1 also applies to the temperature of the raw material liquid when the precipitating agent is added in embodiment 1B.
[0265] The above description regarding the amount of the second precipitant added to the raw material liquid in embodiment 1A-1 (the above description regarding the molar amount of hydroxide ions in the raw material liquid) also applies to the amount of precipitant added to the raw material liquid in embodiment 1B (the molar amount of hydroxide ions in the raw material liquid).
[0266] In embodiment 1B, "the molar amount of oxygen element required to convert the cerium element, the zirconium element, and the rare earth metal element in the raw material liquid into their oxides" means the molar amount of oxygen element required to convert the cerium element, the zirconium element, and the rare earth metal element in the raw material liquid into their oxides when the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is converted to zirconium hydroxide by a precipitant (for example, when the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is basic zirconium sulfate), and means the molar amount of oxygen element required to convert the cerium element and the rare earth metal element in the raw material liquid into their oxides when the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is not converted to zirconium hydroxide by a precipitant (for example, when the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is zirconium hydroxide).
[0267] From the viewpoint of sufficiently precipitating the target hydroxide (cerium hydroxide, optionally zirconium hydroxide, and optionally hydroxide of a rare earth metal element) and improving the OSC of the composite oxide produced in step (1d), it is preferable to age the precipitate while stirring the raw material liquid after adding the precipitant. The ageing time is preferably 1 hour or more and 96 hours or less, more preferably 1 hour or more and 48.0 hours or less, and even more preferably 1 hour or more and 24 hours or less.
[0268] <Embodiment 1C> In embodiment 1C, in step (1a), a raw material liquid is prepared in which the cerium salt and the rare earth metal salt are both poorly water-soluble salts, and the zirconium salt is a water-soluble salt. Embodiment 1C also includes an embodiment in which the raw material liquid prepared in step (1a) does not contain a rare earth metal salt. In an embodiment in which the raw material liquid prepared in step (1a) does not contain a rare earth metal salt, "both the cerium salt and the rare earth metal salt are poorly water-soluble salts, and the zirconium salt is a water-soluble salt" means that the cerium salt is a poorly water-soluble salt, and the zirconium salt is a water-soluble salt.
[0269] In embodiment 1C, a precipitant that precipitates zirconium ions as a poorly water-soluble zirconium salt is used as the precipitant added to the raw material liquid in step (1b).
[0270] In embodiment 1C, in step (1b), it is preferable to add a precipitant selected from an aqueous solution containing sulfate ions and a compound that can be dissolved in water to produce sulfate ions to the raw material liquid to form a first precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element, and then add a reagent selected from an aqueous solution containing hydroxide ions and a compound that can be dissolved in water to produce hydroxide ions to the raw material liquid to treat the first precipitate with hydroxide ions to form a second precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element.
[0271] In step (1b), when a precipitating agent is added to the raw material liquid, a first precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal is formed.
[0272] The cerium element is contained in the first precipitate in the form of a poorly water-soluble salt that was originally contained in the raw material liquid.
[0273] The zirconium element is contained in the first precipitate in the form of basic zirconium sulfate, which is a poorly water-soluble zirconium salt formed by the precipitating agent.
[0274] The rare earth metal element is contained in the first precipitate in the form of a poorly water-soluble salt that was originally contained in the raw material liquid.
[0275] The aluminum element is contained in the first precipitate in the form of aluminum compound particles. The aluminum compound particles originate from the aluminum compound particles originally contained in the raw material liquid. The aluminum compound particles in the raw material liquid are coprecipitated with the poorly water-soluble zirconium salt formed by the precipitating agent.
[0276] The first precipitate contains a poorly water-soluble cerium salt, basic zirconium sulfate, aluminum compound particles, and optionally a poorly water-soluble rare earth metal salt in a mixed state.
[0277] The above description regarding the temperature of the raw material liquid when the first precipitant is added in embodiment 1A-1 also applies to the temperature of the raw material liquid when the precipitant is added in embodiment 1C.
[0278] The above description regarding the amount of the first precipitant added to the raw material liquid in embodiment 1A-1 (the above description regarding the molar amount of sulfate ions in the raw material liquid) also applies to the amount of precipitant added to the raw material liquid in embodiment 1C (the molar amount of sulfate ions in the raw material liquid).
[0279] From the viewpoint of sufficiently precipitating basic zirconium sulfate and improving the OSC of the composite oxide produced in step (1d), it is preferable to age the first precipitate while stirring the raw material liquid after adding the precipitant. The ageing time is preferably 0.1 hours to 10 hours, more preferably 0.2 hours to 5 hours, and even more preferably 0.3 hours to 3 hours.
[0280] After the first precipitate is formed and aged as necessary, a reagent selected from an aqueous solution containing hydroxide ions and a compound that can dissolve in water to produce hydroxide ions is added to the raw material liquid to treat the first precipitate with hydroxide ions, thereby forming a second precipitate containing cerium, zirconium, aluminum, and, in some cases, rare earth metal elements.
[0281] The cerium element is contained in the second precipitate in the form of a poorly water-soluble salt that was originally contained in the raw material liquid, or in the form of cerium hydroxide. When the poorly water-soluble cerium salt originally contained in the raw material liquid is cerium oxide, cerium carbonate, or cerium (IV) sulfate, the poorly water-soluble cerium salt is converted to cerium hydroxide by hydroxide ions. In this case, the cerium element is contained in the second precipitate in the form of cerium hydroxide. When the poorly water-soluble cerium salt originally contained in the raw material liquid is cerium hydroxide, the cerium element is contained in the second precipitate in the form of a poorly water-soluble salt that was originally contained in the raw material liquid (the form of cerium hydroxide).
[0282] The zirconium element is contained in the second precipitate in the form of zirconium hydroxide. Zirconium hydroxide is a poorly water-soluble zirconium salt formed by hydroxide ions. Note that basic zirconium sulfate formed by the precipitating agent is converted to zirconium hydroxide by hydroxide ions.
[0283] The rare earth metal element is contained in the second precipitate in the form of a poorly water-soluble salt that was originally contained in the raw material liquid, or in the form of a hydroxide. If the poorly water-soluble rare earth metal salt originally contained in the raw material liquid is an oxide or a carbonate, the poorly water-soluble rare earth metal salt is converted to a hydroxide of the rare earth metal element by hydroxide ions. In this case, the rare earth metal element is contained in the second precipitate in the form of a hydroxide. If the poorly water-soluble rare earth metal salt originally contained in the raw material liquid is a hydroxide of the rare earth metal element, the rare earth metal element is contained in the second precipitate in the form of a poorly water-soluble salt (hydroxide) that was originally contained in the raw material liquid.
[0284] The aluminum element is contained in the second precipitate in the form of aluminum compound particles. The aluminum compound particles are derived from the aluminum compound particles originally contained in the raw material liquid. Note that at least a portion of the aluminum compound particles contained in the first precipitate is usually contained in the second precipitate as it is.
[0285] The second precipitate contains composite salt particles containing a poorly water-soluble cerium salt (when the poorly water-soluble cerium salt originally contained in the raw material liquid is cerium oxide, cerium carbonate, or cerium (IV) sulfate, the poorly water-soluble cerium salt is converted to cerium hydroxide by hydroxide ions), zirconium hydroxide, and optionally a poorly water-soluble rare earth metal salt (when the poorly water-soluble rare earth metal salt originally contained in the raw material liquid is an oxide or carbonate, the poorly water-soluble rare earth metal salt is converted to a hydroxide of a rare earth metal element by hydroxide ions), and aluminum compound particles in a mixed state. In addition to the composite salt particles, the second precipitate may contain poorly water-soluble cerium salt particles, cerium hydroxide particles, zirconium hydroxide particles, poorly water-soluble rare earth metal salt particles, hydroxide particles of a rare earth metal element, etc. The composite salt particles are formed, for example, by the adhesion and growth of a poorly water-soluble cerium salt (if the poorly water-soluble cerium salt originally contained in the raw material liquid was cerium oxide, cerium carbonate, or cerium (IV) sulfate, the poorly water-soluble cerium salt is converted to cerium hydroxide by hydroxide ions) and / or a poorly water-soluble rare earth metal salt (if the poorly water-soluble rare earth metal salt originally contained in the raw material liquid was an oxide or carbonate, the poorly water-soluble rare earth metal salt is converted to a hydroxide of the rare earth metal element by hydroxide ions) on the surface of basic zirconium sulfate formed by the precipitant (the basic zirconium sulfate is converted to zirconium hydroxide by hydroxide ions).
[0286] The above description regarding the temperature of the source liquid when the second precipitant is added in embodiment 1A-1 also applies to the temperature of the source liquid when the reagent is added in embodiment 1C.
[0287] The above explanation regarding the amount of the second precipitant added to the raw material liquid in embodiment 1A-1 (the above explanation regarding the molar amount of hydroxide ions in the raw material liquid) also applies to the amount of reagent added to the raw material liquid in embodiment 1C (the molar amount of hydroxide ions in the raw material liquid).
[0288] In embodiment 1C, "the molar amount of oxygen element required to convert the cerium element, the zirconium element, and the rare earth metal element in the raw material liquid into oxides" means the molar amount of oxygen element required to convert the cerium element, the zirconium element, and the rare earth metal element in the raw material liquid into oxides when the poorly water-soluble cerium salt and the poorly water-soluble rare earth metal salt originally contained in the raw material liquid are converted into cerium hydroxide and hydroxides of the rare earth metal elements, respectively, by the reagent. When the poorly water-soluble cerium salt originally contained in the raw material liquid is converted into cerium hydroxide by the reagent, and the poorly water-soluble rare earth metal salt originally contained in the raw material liquid is not converted into hydroxides of the rare earth metal elements by the reagent, the cerium element in the raw material liquid is not converted into hydroxides of the rare earth metal elements by the reagent. In the case where the poorly water-soluble cerium salt originally contained in the raw material liquid is not converted to cerium hydroxide by the reagent, and the poorly water-soluble rare earth metal salt originally contained in the raw material liquid is converted to a hydroxide of the rare earth metal element by the reagent, it means the molar amount of oxygen required to convert the zirconium element and the rare earth metal element in the raw material liquid into an oxide; in the case where the poorly water-soluble cerium salt and the poorly water-soluble rare earth metal salt originally contained in the raw material liquid are not converted to cerium hydroxide and a hydroxide of the rare earth metal element by the reagent, it means the molar amount of oxygen required to convert the zirconium element in the raw material liquid into an oxide.
[0289] From the viewpoint of sufficiently precipitating the target hydroxides (zirconium hydroxide, cerium hydroxide, and optionally hydroxides of rare earth metal elements) and improving the OSC of the composite oxide produced in step (1d), it is preferable to age the second precipitate while stirring the raw material liquid after adding the reagents. The ageing time is preferably 1 hour or more and 96 hours or less, more preferably 1 hour or more and 48 hours or less, and even more preferably 1 hour or more and 24 hours or less.
[0290] In embodiment 1C, in step (1c), it is preferable to separate the second precipitate from the raw material liquid subjected to step (1b) to obtain a cake containing the second precipitate.
[0291] In embodiment 1C, in step (1d), it is preferable to calcinate the cake containing the second precipitate obtained in step (1c) to produce a composite oxide containing cerium, zirconium, aluminum, and optionally a rare earth metal element.
[0292] <Second manufacturing method> The second manufacturing method will be described below. The above description of the first manufacturing method also applies to the second manufacturing method, unless otherwise specified.
[0293] The second method includes the following steps: (2a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt; (2b) adding a cationic or nonionic water-soluble polymer and a precipitant to the raw material liquid prepared in the step (2a) to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal; (2c) separating the precipitate from the raw material liquid subjected to the step (2b) to obtain a cake containing the precipitate; and (2d) A step of calcining the cake obtained in step (2c) to produce a composite oxide containing cerium, zirconium, aluminum, and optionally rare earth metal elements. Includes.
[0294] In step (2b), a cationic or nonionic water-soluble polymer is added to the raw material liquid before the formation of a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal.
[0295] In step (2b), by adding the cationic or nonionic water-soluble polymer to the raw material liquid before the formation of the precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element, the cationic or nonionic water-soluble polymer is adsorbed to the surface of the positively charged aluminum compound particles with moderate strength, not with excessive strength. The water-soluble polymer adsorbed to the surface of the aluminum compound particles preferably forms a water-soluble polymer layer.
[0296] The precipitate formed in step (2b) and the cake obtained in step (2c) contain poorly water-soluble salt particles and aluminum compound particles in a mixed state. Examples of poorly water-soluble salt particles include composite salt particles containing poorly water-soluble cerium salt, poorly water-soluble zirconium salt, and optionally poorly water-soluble rare earth metal salt, poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles, etc. From the viewpoint of improving the OSC of the composite oxide produced in step (2d), it is preferable that the precipitate and the cake contain composite salt particles. The precipitate and the cake may contain poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles, etc. in addition to the composite salt particles.
[0297] The water-soluble polymer adsorbed on the surface of the aluminum compound particles (preferably a water-soluble polymer layer formed on the surface of the aluminum compound particles) effectively suppresses aggregation of the aluminum compound particles, thereby improving the dispersibility of the aluminum compound particles in the precipitate formed in step (2b) and the cake obtained in step (2c).
[0298] In the precipitate formed in step (2b) and the cake obtained in step (2c), the poorly water-soluble salt particles are surrounded by aluminum compound particles and water-soluble polymers (preferably water-soluble polymer layers formed on the surfaces of the aluminum compound particles) adsorbed on the surfaces of the aluminum compound particles, which effectively suppresses contact between the poorly water-soluble salt particles. The above-mentioned improvement in dispersibility of the aluminum compound particles also contributes to the suppression of contact between the poorly water-soluble salt particles. By effectively suppressing contact between the poorly water-soluble salt particles, sintering between the poorly water-soluble salt particles is effectively suppressed when the cake is baked in step (2d), and the decrease in the specific surface area of the complex oxide caused by the sintering between the poorly water-soluble salt particles and the decrease in the OSC of the complex oxide caused by the decrease in the specific surface area of the complex oxide are effectively suppressed. Therefore, according to the second manufacturing method, a complex oxide with improved OSC can be manufactured. The second manufacturing method is suitable as a manufacturing method for the complex oxide of the present invention.
[0299] If the raw material liquid prepared in step (2a) does not contain a cationic or nonionic water-soluble polymer, and a cationic or nonionic water-soluble polymer is added to the raw material liquid when a precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element is formed in step (2b) or after the precipitate is formed, contact between the poorly water-soluble salt particles cannot be effectively suppressed in the precipitate formed in step (2b) and in the cake obtained in step (2c), and sintering between the poorly water-soluble salt particles cannot be effectively suppressed when the cake is baked in step (2d).
[0300] Steps (2a) to (2d) will be described below.
[0301] Engineering (2a) Step (2a) is a step of preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt.
[0302] The above explanations regarding step (1a) also apply to step (2a) unless otherwise specified. When applied, "step (1a)" is read as "step (2a)", "step (1b)" is read as "step (2b)", "step (1c)" is read as "step (2c)", and "step (1d)" is read as "step (2d)".
[0303] Step (2a) may include a step of preparing a raw material liquid. For example, the raw material liquid can be prepared by mixing a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt in water. The mixing order of the components is not particularly limited. For example, the raw material liquid can be prepared by dispersing aluminum compound particles in water, and then adding and mixing a cerium salt, a zirconium salt, and optionally a rare earth metal salt to the obtained dispersion.
[0304] From the viewpoint of obtaining a desired precipitate in step (2b), the raw material liquid is preferably stirred to disperse the aluminum compound particles in the raw material liquid before subjecting it to step (2b).
[0305] Engineering (2b) Step (2b) is a step of adding a cationic or nonionic water-soluble polymer and a precipitant to the raw material liquid prepared in step (2a) to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal.
[0306] The above explanations regarding step (1b) also apply to step (2b) unless otherwise specified. When applying, "step (1a)" shall be read as "step (2a)", "step (1b)" as "step (2b)", "step (1c)" as "step (2c)" and "step (1d)" as "step (2d)".
[0307] The cationic water-soluble polymer and the nonionic water-soluble polymer have been described above.
[0308] In step (2b), a cationic or nonionic water-soluble polymer is added to the raw material liquid before a precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element is formed. The cationic or nonionic water-soluble polymer may be added to the raw material liquid multiple times.
[0309] "Adding a cationic or nonionic water-soluble polymer to the raw material liquid" encompasses embodiments in which one or more cationic water-soluble polymers and no nonionic water-soluble polymer are added to the raw material liquid, embodiments in which one or more nonionic water-soluble polymers and no cationic water-soluble polymer are added to the raw material liquid, and embodiments in which one or more cationic water-soluble polymers and one or more nonionic water-soluble polymers are added to the raw material liquid.
[0310] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the percentage of the amount of water-soluble polymer added to the raw material liquid relative to the amount of aluminum compound particles in the raw material liquid is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more. The upper limit can be appropriately adjusted, but is preferably 200% by mass or less, more preferably 100% by mass or less, and even more preferably 50% by mass or less. Each of these upper limits may be combined with any of the above-mentioned lower limits. When the raw material liquid contains one type of aluminum compound particles, the "amount of aluminum compound particles in the raw material liquid" means the amount of the one type of aluminum compound particles, and when the raw material liquid contains two or more types of aluminum compound particles, the total amount of the two or more types of aluminum compound particles. The "amount of water-soluble polymer added to the raw material liquid" means the amount of one type of water-soluble polymer selected from a cationic water-soluble polymer and a nonionic water-soluble polymer when the raw material liquid is added with respect to the one type of water-soluble polymer, and means the total amount of the two or more types of water-soluble polymers selected from a cationic water-soluble polymer and a nonionic water-soluble polymer when the raw material liquid is added with respect to the two or more types of water-soluble polymers.
[0311] Engineering (2c) The step (2c) is a step of separating the precipitate from the raw material liquid subjected to the step (2b) to obtain a cake containing the precipitate.
[0312] The above explanation regarding step (1c) also applies to step (2c) unless otherwise specified. When applying, "step (1a)" is read as "step (2a)", "step (1b)" is read as "step (2b)", "step (1c)" is read as "step (2c)" and "step (1d)" is read as "step (2d)".
[0313] Engineering (2d) The step (2d) is a step of calcining the cake obtained in the step (2c) to produce a composite oxide containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal.
[0314] The above explanation regarding step (1d) also applies to step (2d) unless otherwise specified. When applying, "step (1a)" shall be read as "step (2a)", "step (1b)" as "step (2b)", "step (1c)" as "step (2c)" and "step (1d)" as "step (2d)".
[0315] In the cake obtained in step (2c), between the poorly water-soluble salt particles, there are aluminum compound particles and a water-soluble polymer adsorbed on the surface of the aluminum compound particles (preferably a water-soluble polymer layer formed on the surface of the aluminum compound particles), which effectively suppresses contact between the poorly water-soluble salt particles. By effectively suppressing contact between the poorly water-soluble salt particles, sintering between the poorly water-soluble salt particles is effectively suppressed when the cake is baked in step (2d), and a decrease in the specific surface area of the complex oxide caused by the sintering between the poorly water-soluble salt particles and a decrease in the OSC of the complex oxide caused by the decrease in the specific surface area of the complex oxide are effectively suppressed. Therefore, in step (2d), a complex oxide with improved OSC can be produced. The complex oxide produced in step (2d) is preferably the complex oxide of the present invention.
[0316] The obtained composite oxide may be pulverized as necessary. The pulverization can be carried out according to a conventional method. For example, the pulverization can be carried out in a dry or wet manner using a mortar, a hammer mill, a ball mill, a bead mill, a jet mill, a roller mill, or the like.
[0317] Hereinafter, an embodiment of the second manufacturing method will be described.
[0318] <Embodiment 2A> In embodiment 2A, in step (2a), a raw material liquid is prepared in which the cerium salt, the zirconium salt, and the rare earth metal salt are all water-soluble salts.
[0319] Embodiment 2A corresponds to embodiment 1A. The above explanation regarding embodiment 1A also applies to embodiment 2A unless otherwise specified. When applied, "step (1a)" is replaced with "step (2a)", "step (1b)" is replaced with "step (2b)", "step (1c)" is replaced with "step (2c)", and "step (1d)" is replaced with "step (2d)".
[0320] Embodiment 2A includes Embodiment 2A-1 and Embodiment 2A-2.
[0321] <Embodiment 2A-1> Hereinafter, embodiment 2A-1 will be described.
[0322] In embodiment 2A-1, in step (2b), it is preferable to add a first precipitant selected from an aqueous solution containing sulfate ions and a compound that can be dissolved in water to produce sulfate ions to the raw material liquid to form a first precipitate containing zirconium element and aluminum element, and then add a second precipitant selected from an aqueous solution containing hydroxide ions and a compound that can be dissolved in water to produce hydroxide ions to the raw material liquid to form a second precipitate containing cerium element, zirconium element, aluminum element, and optionally a rare earth metal element.
[0323] Embodiment 2A-1 corresponds to embodiment 1A-1. The above description of embodiment 1A-1 also applies to embodiment 2A-1 unless otherwise specified. When applied, "step (1a)" is replaced with "step (2a)", "step (1b)" is replaced with "step (2b)", "step (1c)" is replaced with "step (2c)", and "step (1d)" is replaced with "step (2d)".
[0324] In embodiment 2A-1, in step (2b), it is preferable to add a cationic or nonionic water-soluble polymer to the raw material solution simultaneously with the addition of the first precipitant, or after the addition of the first precipitant and before the addition of the second precipitant. The cationic or nonionic water-soluble polymer may be added to the raw material solution multiple times.
[0325] When a cationic or nonionic water-soluble polymer is added to the raw material liquid simultaneously with the addition of the first precipitant, a mixture of the first precipitant and the cationic or nonionic water-soluble polymer may be added to the raw material liquid.
[0326] <Embodiment 2A-2> Hereinafter, embodiment 2A-2 will be described.
[0327] In embodiment 2A-2, in step (2b), a precipitant selected from an aqueous solution containing hydroxide ions and a compound that can be dissolved in water to generate hydroxide ions is added to the raw material liquid to form a precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element. In embodiment 2A-2, it is not necessary to use a precipitant selected from an aqueous solution containing sulfate ions and a compound that can be dissolved in water to generate sulfate ions.
[0328] Embodiment 2A-2 corresponds to embodiment 1A-2. The above description of embodiment 1A-2 also applies to embodiment 2A-2 unless otherwise specified. When applied, "step (1a)" is replaced with "step (2a)", "step (1b)" is replaced with "step (2b)", "step (1c)" is replaced with "step (2c)", and "step (1d)" is replaced with "step (2d)".
[0329] In embodiment 2A-2, in step (2b), it is preferable to add a cationic or nonionic water-soluble polymer to the raw material solution before adding the precipitant. The cationic or nonionic water-soluble polymer may be added to the raw material solution multiple times.
[0330] <Embodiment 2B> In embodiment 2B, in step (2a), a raw material liquid is prepared in which the cerium salt and the rare earth metal salt are both water-soluble salts, and the zirconium salt is a poorly water-soluble salt.
[0331] Embodiment 2B corresponds to embodiment 1B. The above explanation regarding embodiment 1B also applies to embodiment 2B unless otherwise specified. When applied, "step (1a)" is replaced with "step (2a)", "step (1b)" is replaced with "step (2b)", "step (1c)" is replaced with "step (2c)", and "step (1d)" is replaced with "step (2d)".
[0332] In embodiment 2B, in step (2b), it is preferable to add a precipitant selected from an aqueous solution containing hydroxide ions and a compound that can be dissolved in water to generate hydroxide ions to the raw material liquid to form a precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element. In embodiment 2B, it is not necessary to use a precipitant selected from an aqueous solution containing sulfate ions and a compound that can be dissolved in water to generate sulfate ions.
[0333] In embodiment 2B, in step (2b), it is preferable to add a cationic or nonionic water-soluble polymer to the raw material solution before the addition of the precipitant. The cationic or nonionic water-soluble polymer may be added to the raw material solution multiple times.
[0334] <Embodiment 2C> In embodiment 2C, in step (2a), a raw material liquid is prepared in which the cerium salt and the rare earth metal salt are both poorly water-soluble salts, and the zirconium salt is a water-soluble salt.
[0335] Embodiment 2C corresponds to embodiment 1C. The above description of embodiment 1C also applies to embodiment 2B unless otherwise specified. When applied, "step (1a)" is replaced with "step (2a)", "step (1b)" is replaced with "step (2b)", "step (1c)" is replaced with "step (2c)", and "step (1d)" is replaced with "step (2d)".
[0336] In embodiment 2C, in step (2b), it is preferable to add a precipitant selected from an aqueous solution containing sulfate ions and a compound that can be dissolved in water to produce sulfate ions to the raw material liquid to form a first precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element, and then add a reagent selected from an aqueous solution containing hydroxide ions and a compound that can be dissolved in water to produce hydroxide ions to the raw material liquid to treat the first precipitate with hydroxide ions to form a second precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element.
[0337] In embodiment 2C, in step (2b), it is preferable to add a cationic or nonionic water-soluble polymer to the raw material solution before the addition of the precipitant (before the formation of the first precipitate). The cationic or nonionic water-soluble polymer may be added to the raw material solution multiple times.
[0338] <Third manufacturing method> The third manufacturing method will now be described. The above description of the first manufacturing method also applies to the third manufacturing method, unless otherwise specified.
[0339] The third method includes the following steps: (3a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt; (3b) adding a precipitating agent to the raw material solution prepared in step (3a) to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal; (3c) separating the precipitate from the raw material liquid subjected to the step (3b) to obtain a cake containing the precipitate; (3d) mixing the cake obtained in step (3c) with an anionic or nonionic water-soluble polymer in a solvent to obtain a slurry containing the anionic or nonionic water-soluble polymer; (3e) evaporating the slurry obtained in step (3d) to dryness to obtain a dry product; and (3f) A step of calcining the dried product obtained in the step (3e) to produce a composite oxide containing cerium, zirconium, aluminum, and optionally a rare earth metal element. Includes.
[0340] In the slurry obtained in step (3d), the anionic or nonionic water-soluble polymer is adsorbed to the surface of the positively charged aluminum compound particles with moderate strength, not with excessive strength. The water-soluble polymer adsorbed to the surface of the aluminum compound particles preferably forms a water-soluble polymer layer.
[0341] In step (3d), when the cake obtained in step (3c) is mixed with a cationic water-soluble polymer in a solvent, the cationic water-soluble polymer is unlikely to be adsorbed onto the surface of the aluminum compound particles, and therefore, in step (3d), an anionic or nonionic water-soluble polymer is used which has a higher adsorption property to the surface of the aluminum compound particles than the cationic water-soluble polymer.
[0342] The slurry obtained in step (3d) contains poorly water-soluble salt particles and aluminum compound particles in a mixed state. Examples of poorly water-soluble salt particles include composite salt particles containing poorly water-soluble cerium salt, poorly water-soluble zirconium salt, and optionally poorly water-soluble rare earth metal salt, poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles, etc. From the viewpoint of improving the OSC of the composite oxide produced in step (3f), it is preferable that the slurry contains composite salt particles. In addition to the composite salt particles, the slurry may contain poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles, etc.
[0343] The water-soluble polymer adsorbed on the surface of the aluminum compound particles (preferably a water-soluble polymer layer formed on the surface of the aluminum compound particles) effectively suppresses aggregation of the aluminum compound particles, thereby improving the dispersibility of the aluminum compound particles in the slurry obtained in step (3d).
[0344] In the slurry obtained in step (3d), the poorly water-soluble salt particles are separated by aluminum compound particles and water-soluble polymers (preferably water-soluble polymer layers formed on the surfaces of the aluminum compound particles) adsorbed on the surfaces of the aluminum compound particles, which effectively suppresses contact between the poorly water-soluble salt particles. The suppression of contact between the poorly water-soluble salt particles is also due to the improvement in dispersibility of the aluminum compound particles described above.
[0345] In order to ensure that the anionic or nonionic water-soluble polymer is adsorbed on the surface of the aluminum compound particles, in step (3e), the slurry obtained in step (3d) is evaporated to dryness to obtain a dry product. The dry product obtained in step (3e) contains poorly water-soluble salt particles and aluminum compound particles in a mixed state. In the dry product obtained in step (3e), the aluminum compound particles and the water-soluble polymer adsorbed on the surface of the aluminum compound particles (preferably a water-soluble polymer layer formed on the surface of the aluminum compound particles) are present between the poorly water-soluble salt particles, which effectively suppresses contact between the poorly water-soluble salt particles. The above-mentioned improvement in dispersibility of the aluminum compound particles also contributes to suppressing contact between the poorly water-soluble salt particles. By effectively suppressing contact between the poorly water-soluble salt particles, sintering between the poorly water-soluble salt particles is effectively suppressed when the dried product is fired in step (3f), and a decrease in the specific surface area of the complex oxide caused by sintering between the poorly water-soluble salt particles and a decrease in the OSC of the complex oxide caused by a decrease in the specific surface area of the complex oxide are effectively suppressed. Therefore, according to the third production method, a complex oxide with improved OSC can be produced. The third production method is suitable as a production method for the complex oxide of the present invention.
[0346] Steps (3a) to (3f) will be described below.
[0347] Engineering (3a) Step (3a) is a step of preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt.
[0348] The above explanation regarding step (1a) also applies to step (3a) unless otherwise specified. When applying, "step (1a)" shall be read as "step (3a)", "step (1b)" as "step (3b)", "step (1c)" as "step (3c)", "step (1d)" as "step (3f)", and "the cake obtained in step (1c)" as "the dried product obtained in step (3e)".
[0349] Step (3a) may include a step of preparing a raw material liquid. For example, the raw material liquid can be prepared by mixing a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt in water. The order of mixing the components is not particularly limited. For example, the raw material liquid can be prepared by dispersing aluminum compound particles in water, and then adding and mixing a cerium salt, a zirconium salt, and optionally a rare earth metal salt to the obtained dispersion.
[0350] From the viewpoint of obtaining a desired precipitate in step (3b), the raw material liquid is preferably stirred to disperse the aluminum compound particles in the raw material liquid before subjecting it to step (3b).
[0351] Engineering (3b) Step (3b) is a step of adding a precipitating agent to the raw material liquid prepared in step (3a) to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal.
[0352] The above explanation regarding step (1b) also applies to step (3b) unless otherwise specified. When applying, "step (1a)" shall be read as "step (3a)", "step (1b)" as "step (3b)", "step (1c)" as "step (3c)", "step (1d)" as "step (3f)", and "the cake obtained in step (1c)" as "the dried product obtained in step (3e)".
[0353] Engineering (3c) The step (3c) is a step of separating the precipitate from the raw material liquid subjected to the step (3b) to obtain a cake containing the precipitate.
[0354] The above explanation regarding step (1c) also applies to step (3c) unless otherwise specified. When applying, "step (1a)" shall be read as "step (3a)", "step (1b)" as "step (3b)", "step (1c)" as "step (3c)", "step (1d)" as "step (3f)", and "the cake obtained in step (1c)" as "the dried product obtained in step (3e)".
[0355] The cake obtained in step (3c) is preferably washed with a washing liquid before being subjected to step (3d). As the washing liquid, water (e.g., pure water such as ion-exchanged water) can be used. In addition, from the viewpoint of suppressing the elution of components in the precipitate and from the viewpoint of washing and removing sulfur content in the precipitate, a solution containing a sodium salt (sodium hydroxide, sodium carbonate, sodium bicarbonate, etc.), ammonia water, or a solution containing an acid (nitric acid, acetic acid, etc.) can be used as the washing liquid, and the pH of the washing liquid can be adjusted to, for example, 6 to 14.
[0356] Engineering (3D) Step (3d) is a step of mixing the cake obtained in step (3c) with an anionic or nonionic water-soluble polymer in a solvent to obtain a slurry containing the anionic or nonionic water-soluble polymer.
[0357] The solvent used for mixing the cake with the anionic or nonionic water-soluble polymer contains water. The water is preferably pure water such as ion-exchanged water. The solvent may contain one or more organic solvents. The organic solvent may be selected from organic solvents such as alcohol, acetone, dimethyl sulfoxide, and dimethylformamide. The total amount of the one or more organic solvents is usually 50.0 vol% or less, preferably 20.0 vol% or less, based on the volume of the solvent.
[0358] When the cake and the anionic or nonionic water-soluble polymer are mixed in water, the anionic or nonionic water-soluble polymer and water may be added to the cake and mixed, or the cake and water may be added to the anionic or nonionic water-soluble polymer and mixed. When the anionic or nonionic water-soluble polymer and water are added to the cake, the anionic or nonionic water-soluble polymer and water may be added separately to the cake, or a mixture of the anionic or nonionic water-soluble polymer and water may be added to the cake. When the cake and water are added to the anionic or nonionic water-soluble polymer, the cake and water may be added separately to the anionic or nonionic water-soluble polymer, or a mixture of the cake and water may be added to the anionic or nonionic water-soluble polymer.
[0359] "Mixing the cake with an anionic or nonionic water-soluble polymer in water" includes embodiments in which one or more anionic water-soluble polymers are used as the water-soluble polymers to be mixed with the cake, and no nonionic water-soluble polymers are used; embodiments in which one or more nonionic water-soluble polymers are used as the water-soluble polymers to be mixed with the cake, and no anionic water-soluble polymers are used; and embodiments in which one or more anionic water-soluble polymers and one or more nonionic water-soluble polymers are used as the water-soluble polymers to be mixed with the cake.
[0360] From the viewpoint of effectively suppressing the aggregation of aluminum compound particles and the contact of poorly water-soluble salt particles, the percentage of the amount of water-soluble polymer mixed with the cake relative to the amount of solid content of the cake is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. The upper limit can be appropriately adjusted, but is preferably 200% by mass or less, more preferably 100% by mass or less, and even more preferably 50% by mass or less. Each of these upper limits may be combined with any of the above-mentioned lower limits. The "amount of water-soluble polymer mixed with the cake" means the amount of the one water-soluble polymer when one water-soluble polymer selected from anionic water-soluble polymers and nonionic water-soluble polymers is used as the water-soluble polymer mixed with the cake, and means the total amount of the two or more water-soluble polymers when the water-soluble polymer mixed with the cake includes two or more water-soluble polymers selected from anionic water-soluble polymers and nonionic water-soluble polymers.
[0361] The nonionic water-soluble polymer is as described above.
[0362] The anionic water-soluble polymer will now be described.
[0363] <Anionic water-soluble polymer> Anionic water-soluble polymers include water-soluble polymers that contain anionic groups but no cationic groups, and water-soluble polymers that contain both cationic and anionic groups and have an isoelectric point of less than 7. The cationic and anionic groups are described above.
[0364] The anionic water-soluble polymer may be a homopolymer or a copolymer.
[0365] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight-average molecular weight of the anionic water-soluble polymer is preferably 1000 or more, more preferably 2000 or more, and even more preferably 3000 or more. The upper limit can be appropriately adjusted, but is preferably 500000 or less, more preferably 200000 or less, and even more preferably 100000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0366] In one embodiment, the anionic water-soluble polymer may be selected from polyacrylates and polymethacrylates. Preferably, the anionic water-soluble polymer is selected from polyacrylates.
[0367] Examples of polyacrylates include ammonium polyacrylate, methylammonium polyacrylate, dimethylammonium polyacrylate, tetramethylammonium polyacrylate, ethylammonium polyacrylate, propylammonium polyacrylate, butylammonium polyacrylate, guanidinium polyacrylate, and pyridinium polyacrylate.
[0368] Examples of polymethacrylates include ammonium polymethacrylate, methylammonium polymethacrylate, dimethylammonium polymethacrylate, tetramethylammonium polymethacrylate, ethylammonium polymethacrylate, propylammonium polymethacrylate, butylammonium polymethacrylate, guanidinium polymethacrylate, and pyridinium polymethacrylate.
[0369] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight-average molecular weight of the polyacrylic acid salt is preferably 1000 or more, more preferably 2000 or more, and even more preferably 3000 or more. The upper limit can be appropriately adjusted, but is preferably 500000 or less, more preferably 200000 or less, and even more preferably 100000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0370] From the viewpoint of effectively suppressing aggregation between aluminum compound particles and contact between poorly water-soluble salt particles, the weight-average molecular weight of the polymethacrylate is preferably 1000 or more, more preferably 2000 or more, and even more preferably 3000 or more. The upper limit can be appropriately adjusted, but is preferably 500000 or less, more preferably 200000 or less, and even more preferably 100000 or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0371] Engineering (3e) The step (3e) is a step of evaporating the slurry obtained in the step (3d) to dryness to obtain a dry matter.
[0372] By evaporating the slurry to dryness, the solvent in the slurry evaporates, and a dry solid consisting of the solid content of the slurry is obtained. The dry solid is a dried solid, which is different from a cake, which is an undried solid. The slurry can be evaporated to dryness according to a conventional method. When evaporating the slurry to dryness, the drying temperature and drying time can be appropriately adjusted.
[0373] By evaporating the slurry obtained in step (3d) to dryness, it is possible to ensure that the anionic or nonionic water-soluble polymer is adsorbed onto the surfaces of the aluminum compound particles in the dried product.
[0374] Engineering (3f) The step (3f) is a step of calcining the dried product obtained in the step (3e) to produce a composite oxide containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metal.
[0375] The above explanation regarding step (1d) also applies to step (3f) unless otherwise specified. When applying, "step (1a)" shall be read as "step (3a)", "step (1b)" as "step (3b)", "step (1c)" as "step (3c)", "step (1d)" as "step (3f)", and "the cake obtained in step (1c)" as "the dried product obtained in step (3e)".
[0376] The dried product obtained in step (3e) contains poorly water-soluble salt particles and aluminum compound particles in a mixed state. In the dried product obtained in step (3e), between the poorly water-soluble salt particles, there are aluminum compound particles and a water-soluble polymer (preferably a water-soluble polymer layer formed on the surface of the aluminum compound particles) adsorbed on the surface of the aluminum compound particles, which effectively suppresses contact between the poorly water-soluble salt particles. The above-mentioned improvement in dispersibility of the aluminum compound particles also contributes to the suppression of contact between the poorly water-soluble salt particles. By effectively suppressing contact between the poorly water-soluble salt particles, sintering between the poorly water-soluble salt particles is effectively suppressed when the dried product is fired in step (3f), and the decrease in the specific surface area of the complex oxide caused by the sintering between the poorly water-soluble salt particles and the decrease in the OSC of the complex oxide caused by the decrease in the specific surface area of the complex oxide are effectively suppressed. Therefore, according to the third manufacturing method, a complex oxide with improved OSC can be manufactured. The third manufacturing method is suitable as a manufacturing method for the complex oxide of the present invention.
[0377] Hereinafter, an embodiment of the third manufacturing method will be described.
[0378] <Embodiment 3A> In embodiment 3A, in step (3a), a raw material liquid is prepared in which the cerium salt, the zirconium salt, and the rare earth metal salt are all water-soluble salts.
[0379] Embodiment 3A corresponds to embodiment 1A. The above explanations regarding embodiment 1A (including the above explanations regarding embodiment 1A-1 and embodiment 1A-2) also apply to embodiment 3A unless otherwise specified. When applied, "step (1a)" is replaced with "step (3a)", "step (1b)" is replaced with "step (3b)", "step (1c)" is replaced with "step (3c)", "step (1d)" is replaced with "step (3f)", and "cake obtained in step (1c)" is replaced with "dried product obtained in step (3e)".
[0380] <Embodiment 3B> In embodiment 3B, in step (3a), a raw material liquid is prepared in which the cerium salt and the rare earth metal salt are both water-soluble salts, and the zirconium salt is a poorly water-soluble salt.
[0381] Embodiment 3B corresponds to embodiment 1B. The above explanation regarding embodiment 1B also applies to embodiment 3B unless otherwise specified. When applied, "step (1a)" is replaced with "step (3a)", "step (1b)" is replaced with "step (3b)", "step (1c)" is replaced with "step (3c)", "step (1d)" is replaced with "step (3f)", and "cake obtained in step (1c)" is replaced with "dried product obtained in step (3e)".
[0382] <Embodiment 3C> In embodiment 3C, in step (3a), a raw material liquid is prepared in which the cerium salt and the rare earth metal salt are both poorly water-soluble salts, and the zirconium salt is a water-soluble salt.
[0383] Embodiment 3C corresponds to embodiment 1C. The above explanation regarding embodiment 1C also applies to embodiment 3C unless otherwise specified. When applied, "step (1a)" is replaced with "step (3a)", "step (1b)" is replaced with "step (3b)", "step (1c)" is replaced with "step (3c)", "step (1d)" is replaced with "step (3f)", and "cake obtained in step (1c)" is replaced with "dried product obtained in step (3e)". EXAMPLES
[0384] <Example 1> In a container, cerium chloride (cerium oxide equivalent: 3.6 g), zirconium oxychloride (zirconium oxide equivalent: 16.0 g), lanthanum chloride (lanthanum oxide equivalent: 1.2 g), neodymium chloride (neodymium oxide equivalent: 1.2 g) and an yttrium chloride aqueous solution (yttrium oxide equivalent: 1.2 g) were dissolved in pure water to obtain a metal salt aqueous solution.
[0385] In a separate container, pure water and boehmite particles (AlO(OH), amount converted to aluminum oxide: 16.8 g) were added and stirred to disperse the boehmite particles, thereby obtaining a boehmite particle dispersion liquid.
[0386] Median diameter of boehmite particles D 50 The median diameter of the boehmite particles D 50 means the particle size at which the cumulative volume is 50% in the volume-based particle size distribution of boehmite particles measured by dynamic light scattering. The volume-based particle size distribution of boehmite particles measured by dynamic light scattering was measured by dispersing the boehmite particles in 1.5 mass% hydrochloric acid (boehmite particle concentration: 8 mass%) and using a commercially available particle size distribution measuring device ("Zetasizer Nano ZS" manufactured by Malvern Panalytical).
[0387] To the boehmite particle dispersion, poly[2-(ethyldimethylammonio)ethyl methacrylate]] sulfate (weight average molecular weight: 56000) was added, and the previously prepared metal salt aqueous solution was further added, followed by adding pure water so that the total mass became 537.3 g, to obtain a raw material liquid. The amount of poly[2-(ethyldimethylammonio)ethyl methacrylate]] sulfate added was 7 g relative to the solid content of the boehmite particle dispersion of 40 g.
[0388] After the raw material liquid was heated to 85°C, 68.6g of 25% by mass ammonium sulfate aqueous solution was dropped while stirring the raw material liquid. After the dropwise addition, the precipitate was aged at 85°C while stirring the raw material liquid. After the dropwise addition, the raw material liquid was cooled to 40°C, and 136.8g of 25% by mass sodium hydroxide aqueous solution was dropped while stirring the raw material liquid. After the dropwise addition, the precipitate was aged to obtain a slurry. The obtained slurry was suction filtered, and the precipitate was collected as a cake, and the collected cake was washed with pure water. The washed cake was fired in an electric furnace. The fired mass was pulverized to obtain a powder of a composite oxide containing zirconium, cerium, lanthanum, neodymium, yttrium, and aluminum elements.
[0389] The mass ratio of zirconium, cerium, lanthanum, neodymium, yttrium, and aluminum elements contained in the obtained composite oxide powder in terms of oxide (ZrO 2 :CeO 2 :La 2 O 3 :Nd 2 O 3 :Y 2 O 3 :Al 2 O 3 The ratio of each metal element contained in the composite oxide powder in terms of oxide was calculated from the content of each metal element in terms of metal measured by inductively coupled plasma atomic emission spectrometry (ICP-AES). The same applies to the other examples and comparative examples.
[0390] <Example 2> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]] ethyl sulfate was changed to hydroxypropyl methylcellulose (Metolose 60SH-15, weight average molecular weight: 45,000, manufactured by Shin-Etsu Chemical Co., Ltd.).
[0391] <Example 3> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]]ethyl sulfate was changed to polyvinylpyrrolidone (weight average molecular weight: 30,000).
[0392] <Example 4> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]] sulfate was changed to Pluronic P-123 (weight average molecular weight: 5800) manufactured by Sigma-Aldrich. Pluronic P-123 is poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) represented by the following formula (II), where x=20, y=70, and z=20.
[0393] [ka]
[0394] <Example 5> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]]ethyl sulfate was changed to polyethyleneimine (weight average molecular weight: 10,000).
[0395] <Example 6> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]] sulfate was changed to Pluronic F-127 (weight average molecular weight: 12500) manufactured by Sigma-Aldrich. Pluronic F-127 is poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) represented by the above formula (II) where x=106, y=70, and z=106.
[0396] <Example 7> In a container, cerium nitrate (cerium oxide equivalent: 3.6 g), zirconium oxynitrate (zirconium oxide equivalent: 16.0 g), lanthanum nitrate (lanthanum oxide equivalent: 1.2 g), neodymium nitrate (neodymium oxide equivalent: 1.2 g) and an yttrium nitrate aqueous solution (yttrium oxide equivalent: 1.2 g) were dissolved in pure water to obtain a metal salt aqueous solution.
[0397] In a separate container, pure water and boehmite particles (AlO(OH), amount converted to aluminum oxide: 16.8 g) were added and stirred to disperse the boehmite particles, thereby obtaining a boehmite particle dispersion liquid.
[0398] Median diameter of boehmite particles D 50 The median diameter of the boehmite particles D 50 The meaning and measurement method are the same as in Example 1.
[0399] To the boehmite particle dispersion, poly[2-(ethyldimethylammonio)ethyl methacrylate]] sulfate (weight average molecular weight: 56000) was added, and the previously prepared metal salt aqueous solution was further added, followed by adding pure water so that the total mass became 584.3 g, to obtain a raw material solution. The amount of poly[2-(ethyldimethylammonio)ethyl methacrylate]] sulfate added was 7 g relative to the solid content of the boehmite particle dispersion of 40 g.
[0400] While stirring the raw material liquid, 209.1 g of a 10 mass % aqueous ammonia solution was dropped at a temperature of 25°C. After the dropwise addition, the precipitate was aged at a temperature of 25°C to obtain a slurry. The obtained slurry was suction filtered, and the precipitate was collected as a cake, which was washed with pure water. The washed cake was fired in an electric furnace. The fired mass was pulverized to obtain a powder of a composite oxide containing zirconium, cerium, lanthanum, neodymium, yttrium, and aluminum elements.
[0401] The mass ratio of zirconium, cerium, lanthanum, neodymium, yttrium, and aluminum elements contained in the obtained composite oxide powder in terms of oxide (ZrO 2 :CeO 2 :La 2 O 3 :Nd 2 O 3 :Y 2 O 3 :Al 2 O 3 ) was 40.0:9.0:3.0:3.0:3.0:42.0.
[0402] <Example 8> A composite oxide powder was obtained in the same manner as in Example 1, except that the amount of poly[2-(ethyldimethylammonio)ethyl methacrylate]] sulfate added was 1.75 g relative to the solid content of the boehmite particle dispersion of 40 g.
[0403] <Example 9> A composite oxide powder was obtained in the same manner as in Example 1, except that the amount of poly[2-(ethyldimethylammonio)ethyl methacrylate] sulfate added was 0.35 g relative to the solid content of the boehmite particle dispersion of 40 g.
[0404] <Example 10> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate] sulfate was not added to the boehmite particle dispersion liquid, but was added to the ammonium sulfate aqueous solution that was dropped into the raw material liquid.
[0405] <Example 11> In a container, cerium chloride (cerium oxide equivalent: 3.2 g), zirconium oxychloride (zirconium oxide equivalent: 13.9 g), neodymium chloride (neodymium oxide equivalent: 1.2 g) and an yttrium chloride aqueous solution (yttrium oxide equivalent: 0.5 g) were dissolved in pure water to obtain a metal salt aqueous solution.
[0406] In a separate container, pure water and boehmite particles (AlO(OH), amount converted to aluminum oxide: 19.3 g) were added and stirred to disperse the boehmite particles, thereby obtaining a boehmite particle dispersion liquid.
[0407] Median diameter of boehmite particles D 50 The median diameter of the boehmite particles D 50 The meaning and measurement method are the same as in Example 1.
[0408] The metal salt aqueous solution prepared above was added to the boehmite particle dispersion, and then pure water was added so that the total mass became 518.7 g, to obtain a raw material liquid.
[0409] The raw material liquid was heated to 85°C, and 68.6g of 25% by mass ammonium sulfate aqueous solution was dropped while stirring the raw material liquid. After the dropwise addition, the precipitate was aged at 85°C while stirring the raw material liquid. After the dropwise addition, the precipitate was aged to obtain a slurry. The obtained slurry was suction filtered, and the precipitate was collected as a cake, and the collected cake was washed with pure water. Ammonium polyacrylate (Aron A-30SL, weight average molecular weight: 6000, manufactured by Toagosei Co., Ltd.) was added to the washed cake, and then about 6 times the amount of pure water was added to perform reslurry. The amount of ammonium polyacrylate added was 7g relative to the solid content of the cake after washing, 40g. The slurry obtained by the reslurry was evaporated to dryness, and the obtained dryness was fired in an electric furnace. The fired mass was pulverized to obtain a powder of a composite oxide containing elemental zirconium, elemental cerium, elemental lanthanum, elemental neodymium, elemental yttrium, and elemental aluminum.
[0410] The mass ratio of zirconium, cerium, lanthanum, neodymium, yttrium, and aluminum elements contained in the obtained composite oxide powder in terms of oxide (ZrO 2 :CeO 2 :La 2 O 3 :Nd 2 O3 :Y 2 O 3 :Al 2 O 3 ) was 35.0:8.0:0:6.0:3.0:48.0.
[0411] <Example 12> A composite oxide powder was obtained in the same manner as in Example 11, except that ammonium polyacrylate (Aron A-30SL, manufactured by Toagosei Co., Ltd.) was changed to hydroxypropyl methylcellulose (Metolose 60SH-15, weight average molecular weight: 45,000, manufactured by Shin-Etsu Chemical Co., Ltd.).
[0412] <Comparative Example 1> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]]ethyl sulfate was not added.
[0413] <Comparative Example 2> Median diameter D 50 The boehmite particles have a median diameter of 278 nm and a 50 A composite oxide powder was obtained in the same manner as in Comparative Example 1, except that the diameter was changed to 58 nm boehmite particles.
[0414] <Comparative Example 3> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]] sulfate was changed to laurylamine and the amount of laurylamine added was 5 g per 40 g of solid content of the boehmite particle dispersion.
[0415] <Comparative Example 4> A composite oxide powder was obtained in the same manner as in Comparative Example 3, except that the amount of laurylamine added was changed to 1 g per 40 g of the solid content of the boehmite particle dispersion.
[0416] <Comparative Example 5> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]] sulfate was changed to decyl glucoside and the amount of decyl glucoside added was 5 g per 40 g of solid content of the boehmite particle dispersion.
[0417] <Comparative Example 6> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]]ethyl sulfate was changed to polyammonium acrylate (Aron A-30L, weight average molecular weight: 6000, manufactured by Toagosei Co., Ltd.).
[0418] <Comparative Example 7> A composite oxide powder was obtained in the same manner as in Example 7, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]]ethyl sulfate was not added.
[0419] <Comparative Example 8> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate] sulfate was not added to the boehmite particle dispersion liquid, but was added to the sodium hydroxide aqueous solution dropped into the raw material liquid.
[0420] <Comparative Example 9> A composite oxide powder was obtained in the same manner as in Example 1, except that poly[2-(ethyldimethylammonio)ethyl methacrylate] sulfate was not added to the boehmite particle dispersion liquid, but was added to the raw material liquid after the dropwise addition of the sodium hydroxide aqueous solution.
[0421] <Comparative Example 10> A composite oxide powder was obtained in the same manner as in Example 7, except that poly[2-(ethyldimethylammonio)ethyl methacrylate]] sulfate was not added to the boehmite particle dispersion liquid, but was added to the aqueous ammonia solution dropped into the raw material liquid.
[0422] <Comparative Example 11> A composite oxide powder was obtained in the same manner as in Example 11, except that ammonium polyacrylate (Aron A-30SL manufactured by Toagosei Co., Ltd.) was changed to polyethyleneimine (weight average molecular weight: 6000).
[0423] <Measurement of OSC amount> The OSC amounts of the composite oxides obtained in Examples 1 to 12 and Comparative Examples 1 to 10 were measured by the CO pulse method as follows.
[0424] After supporting 1 part by mass of rhodium element in terms of metal per 100 parts by mass of the composite oxide on the composite oxide, the sample was prepared by heat-treating in the atmosphere at 1000 ° C for 25 hours. Specifically, it is as follows. The composite oxide of the present invention was dispersed in an aqueous solution of a water-soluble rhodium salt (for example, rhodium nitrate), and after evaporating the solvent while stirring, it was fired in the atmosphere at 600 ° C for 1 hour, so that 1 part by mass of rhodium element in terms of metal was supported per 100 parts by mass of the composite oxide. The prepared powder was heat-treated in the atmosphere at 1000 ° C for 25 hours, and this was used as a sample.
[0425] The sample was packed in a sample tube, heated to 800 ° C under an argon stream, and then cooled to 400 ° C. Using the sample obtained at 400 ° C in this way, the following operation (A) was performed, and CeO 2 The OSC amount per gram was calculated, and this was defined as the OSC amount of the composite oxide at 400 ° C per gram of CeO 2 1 g of the composite oxide at 400 ° C per gram of CeO
[0426] [Operation (A)] Oxygen was passed through the sample tube, and then helium was passed through. Subsequently, a mixed gas (1 atm, 0 ° C) containing 25% by volume of CO and 75% by volume of helium was passed through 15 times at a flow rate of 50 cc / min, and the CeO contained in the sample 2 and Rh 2 O 3The amount of CO contained in the gas after contact was measured, and the amount of CO reduction (μmol) was calculated. The measurement device used was a Microtrack-Bel "BELMETAL." Using the amount of CO reduction calculated by the above procedure, the CeO 2 The amount of OSC per gram (μmol / g) was calculated. CEO 2 Amount of OSC per 1g = amount of CO reduced (μmol) / CeO in sample 2 Content (g)
[0427] The results are shown in Table 1.
[0428] [Table 1]
[0429] As shown in Table 1, according to the first, second and third production methods of the present invention, composite oxides containing cerium, zirconium, aluminum and, in some cases, rare earth metal elements other than cerium, and having improved OSC (particularly, OSC after exposure to a high-temperature environment), specifically, CeO 2 It was possible to produce a composite oxide with an OSC amount of 1470 μmol / g or more per gram at 400°C.
Claims
1. A composite oxide containing cerium, zirconium, aluminum, and optionally a rare earth metal element other than cerium, CeO measured by CO pulse method 2 The composite oxide has an OSC amount per gram at 400° C. of 1470 μmol / g or more.
2. The following steps: (1a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, a cationic or nonionic water-soluble polymer, and optionally a rare earth metal salt other than a cerium salt; (1b) adding a precipitating agent to the raw material liquid to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium; (1c) separating the precipitate from the raw material liquid to obtain a cake containing the precipitate; and (1d) A step of calcining the cake to produce a composite oxide containing cerium, zirconium, aluminum, and optionally rare earth metal elements other than cerium. A method for producing a complex oxide, comprising: the aluminum compound particles are selected from alumina particles and alumina hydrate particles; The median diameter D of the aluminum compound particles measured by dynamic light scattering method 50 is 1 nm or more and 500 nm or less.
3. 3. The method according to claim 2, wherein in step (1a), a percentage of the amount of the water-soluble polymer in the raw material solution relative to the amount of the aluminum compound particles in the raw material solution is 0.1 mass% or more.
4. The following steps: (2a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt other than the cerium salt; (2b) adding a cationic or nonionic water-soluble polymer and a precipitant to the raw material liquid to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium; (2c) separating the precipitate from the raw material liquid to obtain a cake containing the precipitate; and (2d) A step of calcining the cake to produce a composite oxide containing cerium, zirconium, aluminum, and optionally rare earth metal elements other than cerium. A method for producing a complex oxide, comprising: In step (2b), the water-soluble polymer is added to the raw material liquid before the precipitate is formed; the aluminum compound particles are selected from alumina particles and alumina hydrate particles; The median diameter D of the aluminum compound particles measured by dynamic light scattering method 50 is 1 nm or more and 500 nm or less.
5. 5. The method according to claim 4, wherein in the step (2b), a percentage of an amount of the water-soluble polymer added to the raw material liquid relative to an amount of the aluminum compound particles in the raw material liquid is 0.1 mass% or more.
6. The method according to any one of claims 2 to 5, wherein the cationic water-soluble polymer has a repeating unit containing a quaternary ammonium group, and the molecular weight of the repeating unit is 180 or more.
7. The method according to claim 6 , wherein the weight average degree of polymerization of the repeating unit is 20 or more.
8. The following steps: (3a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt other than the cerium salt; (3b) adding a precipitating agent to the raw material liquid to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally elemental rare earth metals other than elemental cerium; (3c) separating the precipitate from the raw material liquid to obtain a cake containing the precipitate; (3d) mixing the cake with an anionic or nonionic water-soluble polymer in a solvent to obtain a slurry containing the water-soluble polymer; (3e) evaporating the slurry to dryness to obtain a dry product; and (3f) A step of calcining the dried product to produce a composite oxide containing cerium, zirconium, aluminum, and optionally rare earth metal elements other than cerium. A method for producing a complex oxide, comprising: the aluminum compound particles are selected from alumina particles and alumina hydrate particles; The median diameter D of the aluminum compound particles measured by dynamic light scattering method 50 is 1 nm or more and 500 nm or less.
9. The method according to claim 8, wherein in step (3d), the percentage of the amount of the water-soluble polymer mixed with the cake relative to the amount of solids in the cake is 5 mass% or more.
Citation Information
Patent Citations
Composite oxide and method for producing same
WO2022137910A1
Cited By
Superfine lanthanum zirconate powder and preparation method thereof
CN120887451A